Photo-crosslinkable adhesive and its application

By using a photocrosslinking adhesive of a polymer with a benzophenone structure in the side chain, combined with an ethylenically unsaturated compound and a BP polymer, the problem that existing adhesives are difficult to achieve surface shape follow-up and deformation resistance at the same time is solved, and the bonding durability and reliability in high temperature environments are achieved, and the VOC dissipation amount is reduced.

CN114144488BActive Publication Date: 2025-04-04NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080052401.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-02
Filing Date
2020-07-28
Publication Date
2025-04-04
Estimated Expiration
2040-07-28

AI Technical Summary

Technical Problem

It is difficult for existing adhesives to achieve surface shape compliance and deformation resistance at the same time, especially in high temperature environments, which easily produces bubbles, which affects the reliability of bonding.

Method used

The photocrosslinking adhesive is used to include a polymer having a benzophenone structure in the side chain, and the deformation resistance of the adhesive is improved by photocrosslinking, and an ethylenically unsaturated compound and a BP polymer are preferably used in the adhesive composition to control the VOC dissipation amount to 500 μg/g or less.

Benefits of technology

The adhesive with good surface shape following is realized, which can suppress bubble formation in a high temperature environment, improve the durability and reliability of bonding, and reduce the odor and environmental pollution of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003478191810000121
    Figure BDA0003478191810000121
  • Figure BDA0003478191810000131
    Figure BDA0003478191810000131
  • Figure BDA0003478191810000261
    Figure BDA0003478191810000261
Patent Text Reader

Abstract

The present invention can provide a photo-crosslinkable adhesive comprising a polymer having a benzophenone structure in a side chain. The photo-crosslinkable adhesive is a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a component containing a benzophenone structure. The emission of volatile organic compounds of the photo-crosslinkable adhesive is 500 μg / g or less. In addition, the present invention can provide an adhesive sheet having an adhesive layer formed of the photo-crosslinkable adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photo-crosslinkable adhesive, a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing the photo-crosslinkable adhesive, a method for producing a laminate using the photo-crosslinkable adhesive, a method for producing the photo-crosslinkable adhesive, and a pressure-sensitive adhesive composition used in the production of the photo-crosslinkable adhesive.

[0002] This application claims priority based on Japanese Patent Application No. 2019-143392 filed on August 2, 2019, the entire contents of which are incorporated herein by reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives, hereinafter the same) have the following properties: they are in a soft solid (viscoelastic) state in a temperature range near room temperature and are easily adhered to an adherend under pressure. Due to such properties, adhesives are widely used in various fields. Patent Document 1 can be cited as a technical document related to adhesives.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-140497 Summary of the invention

[0007] Problems to be solved by the invention

[0008] For adhesives, various properties are required according to the purpose. Among these properties, it is sometimes difficult to achieve them at a high level at the same time, for example, there is a tendency for another property to decrease when one property is desired to be improved. As an example of a property in such a relationship that is difficult to achieve at the same time, the property of deforming by following the surface shape of the adherend (hereinafter, also referred to as "surface shape following property") and the property of not being easy to deform relative to stress (hereinafter, also referred to as "deformation resistance").

[0009] Therefore, an object of the present invention is to provide an adhesive having good conformability to the surface shape of an adherend and capable of forming a bond having high deformation resistance, and an adhesive sheet using the adhesive.

[0010] Means for solving problems

[0011] According to the present description, a photo-crosslinkable adhesive including a polymer having a benzophenone structure in a side chain can be provided.

[0012] The photo-crosslinkable adhesive can be photo-crosslinked using the benzophenone structure after being attached to the adherend, thereby improving the deformation resistance of the adhesive. As a result, the adhesive has good surface shape tracking when attached to the adherend, and after attachment, a bond with high deformation resistance can be formed by photo-crosslinking. For an adhesive with good surface shape tracking, it can be appropriately adhered to the surface of the adherend by deforming along the step difference that may exist on the surface of the adherend (absorbing the step difference).

[0013] In addition, in the adherend of the adhesive, there is a substance that produces so-called outgassing under conditions such as high temperature environment. In such an adherend, even if a good adhesion state without bubbles is temporarily achieved between the adhesive and the adherend, there may be a situation in which outgassing from the adherend is accumulated at the interface between the adhesive and the adherend to form new bubbles. The generation of the bubbles (foaming) will reduce the adhesion area of ​​the adhesive to the adherend, thereby reducing the reliability of the bonding based on the adhesive. Therefore, for the adhesive that is assumed to be bonded to the adherend that is prone to outgassing, it is expected to be constructed to be able to suppress the formation of the above-mentioned bubbles even if it is kept in a high temperature environment after being attached to the adherend and to be closely attached to the above-mentioned adherend with good durability. The above-mentioned bubbles deform the adhesive and are formed, so improving the deformation resistance of the adhesive can help to suppress the formation of bubbles. The photo-crosslinkable adhesive disclosed herein can be photo-crosslinked after being attached to the adherend to improve the deformation resistance of the adhesive. Therefore, according to the photo-crosslinkable adhesive, surface shape tracking and close adhesion durability can be appropriately achieved at the same time.

[0014] In some embodiments of the technology disclosed herein (including a photocrosslinkable adhesive, a method for producing an adhesive sheet and a laminate using the photocrosslinkable adhesive, a method for producing a photocrosslinkable adhesive, an adhesive composition used in the production of a photocrosslinkable adhesive, etc., the same below), the emission of volatile organic compounds of the photocrosslinkable adhesive is 500 μg / g or less. Thus, a photocrosslinkable adhesive having a low emission of volatile organic compounds (VOC) (hereinafter also referred to as "VOC emission") is low in odor and is preferred from the perspective of environmental hygiene.

[0015] The photo-crosslinkable adhesive disclosed herein may be a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a benzophenone structural component. Non-limiting examples of the above-mentioned benzophenone structural component include polymers having a benzophenone structure in the side chain (hereinafter also referred to as "BP polymers"), and compounds having an ethylenically unsaturated group and a benzophenone structure in the molecule (hereinafter also referred to as "ethylenically unsaturated BP".). In some embodiments, a BP polymer may be preferably used as the above-mentioned benzophenone structural component. The photo-crosslinkable adhesive disclosed herein may preferably be a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a BP polymer.

[0016] According to the present specification, a photo-crosslinkable adhesive comprising two or more polymers having different monomer compositions, and at least one of the above two or more polymers is a BP polymer, can also be provided. According to the photo-crosslinkable adhesive comprising two or more polymers as described above, the properties of the photo-crosslinkable adhesive and the properties of the photo-crosslinked product of the photo-crosslinkable adhesive (i.e., the above photo-crosslinkable adhesive after photo-crosslinking) can be appropriately adjusted by selecting and combining their polymers. The above photo-crosslinkable adhesive comprising two or more polymers can be, for example, a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a BP polymer. The VOC emission of the above photo-crosslinkable adhesive comprising two or more polymers is preferably 500 μg / g or less.

[0017] In some embodiments, the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive disclosed herein at 80°C and the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive disclosed herein at 80°C using a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The relationship of the shear storage elastic modulus Gc'[kPa] at 80°C of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays under the conditions can satisfy the following formula: Gc'[kPa]-Gb'[kPa]≥2kPa. Hereinafter, the shear storage elastic modulus Gb' is sometimes referred to as "elastic modulus Gb' before photo-crosslinking" or simply "elastic modulus Gb'", and the shear storage elastic modulus Gc' is sometimes referred to as "elastic modulus Gc' after photo-crosslinking" or simply "elastic modulus Gc'". In addition, below, Gc'[kPa]-Gb'[kPa], that is, the increase in the shear storage elastic modulus at 80°C based on photo-crosslinking, is sometimes referred to as "ΔG'" (unit: kPa). According to the photo-crosslinkable adhesive with ΔG' of 2kPa or more, the effect of improving deformation resistance brought about by photo-crosslinking can be easily and appropriately exerted.

[0018] In some embodiments, for the photo-crosslinkable adhesive disclosed herein, a high pressure mercury lamp is used with an illumination of 300 mW / cm 2、Accumulated light intensity 10000mJ / cm 2 The shear storage elastic modulus Gc' [kPa] of the photocrosslinked product obtained by irradiating the photocrosslinkable adhesive with ultraviolet rays at 80°C can be 40 kPa or more. Photocrosslinkable adhesives having an elastic modulus Gc' of 40 kPa or more after photocrosslinking tend to exhibit excellent adhesion durability to the adherend by photocrosslinking after being attached to the adherend, so they are preferred.

[0019] According to the present specification, there is provided an adhesive sheet having an adhesive layer formed of any photo-crosslinkable adhesive disclosed herein, wherein the photo-crosslinkable adhesive layer has good surface shape followability when attached to an adherend, and can form a bond with high deformation resistance by photo-crosslinking the photo-crosslinkable adhesive after attachment.

[0020] In some embodiments, the peel strength of the adhesive sheet measured by the following procedure may be 1.0 N / 10 mm or more. According to the adhesive sheet having such peel strength, highly reliable bonding can be preferably achieved.

[0021] [Peel strength measurement procedure]

[0022] The surface of the adhesive layer was pressed against the glass plate by reciprocating a 2 kg rubber roller, and then autoclaved (50° C., 0.5 MPa, 15 minutes). Then, a high pressure mercury lamp was used to heat the glass plate at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The glass plate was irradiated with ultraviolet rays from the glass plate side under the conditions of , and then the adhesive sheet was peeled off from the glass plate at a tension speed of 300 mm / min and a peeling angle of 180 degrees in an atmosphere of 25° C., and the peel strength at this time was measured.

[0023] According to the present specification, a method for manufacturing a laminated body can be provided, which sequentially includes the following steps: laminating any photo-crosslinkable adhesive disclosed herein and a component; and reacting the benzophenone structure contained in the photo-crosslinkable adhesive to photo-crosslink the photo-crosslinkable adhesive. According to this method, when the photo-crosslinkable adhesive is laminated on the component, the photo-crosslinkable adhesive can be made to follow the surface shape of the component well, and after lamination, the photo-crosslinkable adhesive is photo-crosslinked to improve deformation resistance, so that a laminated body in which the photo-crosslinked product of the photo-crosslinkable adhesive is reliably bonded to the component can be obtained.

[0024] According to the present specification, a method for producing a photocrosslinkable adhesive comprising the following steps can be provided: preparing an adhesive composition comprising a BP polymer (A) and an ethylenically unsaturated compound (B); and irradiating the above-mentioned adhesive composition with active energy rays. The irradiation with the above-mentioned active energy rays is carried out in a manner that the ethylenically unsaturated group possessed by the above-mentioned ethylenically unsaturated compound (B) reacts and the benzophenone structure possessed by the above-mentioned BP polymer (A) remains. Thus, a photocrosslinkable adhesive comprising a BP polymer can be obtained in the form of an active energy ray cured product of the above-mentioned adhesive composition. The above-mentioned production method can be preferably adopted as a method for producing any photocrosslinkable adhesive disclosed herein.

[0025] In some embodiments, the adhesive composition may include a compound (B1) having one ethylenically unsaturated group as the ethylenically unsaturated compound (B). According to the adhesive composition of the embodiment, the properties of the photo-crosslinkable adhesive formed by the composition can be appropriately adjusted by selecting the type and amount of the compound (B1).

[0026] In some embodiments, the adhesive composition may include a compound (B2) having two or more ethylenically unsaturated groups as the ethylenically unsaturated compound (B). According to the adhesive composition of the embodiment, the properties of the photo-crosslinkable adhesive formed by the composition can be appropriately adjusted by selecting the type and amount of the compound (B2).

[0027] In some embodiments, the adhesive composition may further include a photoinitiator (C). By using a photoinitiator (C), the reaction of the ethylenically unsaturated group possessed by the ethylenically unsaturated compound (B) can be promoted. As the photoinitiator (C), a compound that generates free radicals by absorbing light with a wavelength of 300nm to 500nm can be preferably used. The excitation wavelength of the benzophenone structure is usually lower than 300nm, so by using a photoinitiator that generates free radicals by absorbing light with a wavelength of more than 300nm, the reaction of the ethylenically unsaturated group can be effectively promoted while leaving the benzophenone structure residual.

[0028] As the active energy ray irradiated to the adhesive composition, for example, ultraviolet rays substantially free of components having a wavelength of less than 300 nm can be preferably used. The ultraviolet rays can cure the adhesive composition while leaving the benzophenone structure and reacting the ethylenically unsaturated groups, thereby suitably manufacturing a photo-crosslinkable adhesive containing a BP polymer.

[0029] According to the present specification, an adhesive composition used in the manufacture of a photo-crosslinkable adhesive containing a BP polymer can be provided. The above-mentioned adhesive composition comprises a BP polymer (A) and an ethylenically unsaturated compound (B). The above-mentioned photo-crosslinkable adhesive can be manufactured by curing the adhesive composition in a manner that the ethylenically unsaturated group of the above-mentioned ethylenically unsaturated compound (B) reacts and the benzophenone structure of the above-mentioned BP polymer (A) remains. The curing of the above-mentioned adhesive composition can be carried out, for example, by irradiating the above-mentioned adhesive composition with active energy rays.

[0030] In some embodiments, the adhesive composition may contain a photoinitiator (C) that generates free radicals by absorbing light with a wavelength of 300 nm to 500 nm. By using the photoinitiator (C), the reaction of the ethylenically unsaturated group can be effectively promoted while the benzophenone structure remains.

[0031] In some embodiments, the adhesive composition preferably has a weight fraction of the compound having two or more ethylenically unsaturated groups in the total monomer components constituting the adhesive composition of less than 5 weight percent. The adhesive composition of the composition tends to form a photo-crosslinkable adhesive that exhibits good surface shape followability before photo-crosslinking.

[0032] It should be noted that appropriate combinations of the above-mentioned elements may also be included in the scope of the invention claimed for patent protection in this international application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] [ Figure 1 ] Figure 1 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.

[0034] [ Figure 2 ] Figure 2 This is a cross-sectional view schematically showing the structure of a pressure-sensitive adhesive sheet according to another embodiment.

[0035] [ Figure 3 ] Figure 3 This is a cross-sectional view schematically showing an optical member with a pressure-sensitive adhesive sheet in which a pressure-sensitive adhesive sheet according to one embodiment is attached to an optical member. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention are described below. It should be noted that matters necessary for implementing the present invention, except for those specifically mentioned in this specification, can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, components and parts that play the same role are sometimes marked with the same symbols for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are illustrated for the purpose of clearly explaining the present invention, and do not necessarily accurately represent the size or reduction ratio of the product actually provided.

[0037] In this specification, "acrylic polymer" refers to a polymer derived from a monomer component containing an acrylic monomer in an amount of more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight). The above-mentioned acrylic monomer refers to a monomer having at least one (meth)acryloyl group in one molecule. In addition, in this specification, "(meth)acryloyl" refers to both acryloyl and methacryloyl. Similarly, "(meth)acrylate" refers to both acrylate and methacrylate, and "(meth)acrylic-" refers to both acrylic- and methacrylic-, respectively.

[0038] In this specification, "ethylenically unsaturated compound" refers to a compound having at least one ethylenically unsaturated group in the molecule. Examples of ethylenically unsaturated groups include (meth)acryloyl, vinyl, allyl, etc. Hereinafter, a compound having one ethylenically unsaturated group is sometimes referred to as a "monofunctional monomer", and a compound having more than two ethylenically unsaturated groups is sometimes referred to as a "multifunctional monomer". In addition, a compound having X ethylenically unsaturated groups in a multifunctional monomer is sometimes described as "X-functional monomer".

[0039] In this specification, the adhesive composition contains an ethylenically unsaturated compound, and unless otherwise specified, it means that the adhesive composition contains the ethylenically unsaturated compound in the form of a partial polymer. Such a partial polymer is usually a mixture of the ethylenically unsaturated compound (unreacted monomer) containing an ethylenically unsaturated group and the ethylenically unsaturated compound polymerized with the ethylenically unsaturated group.

[0040] In this specification, the so-called monomer components constituting the adhesive composition as a whole refers to the total amount of monomer components constituting the polymer contained in the adhesive composition and the monomer components contained in the adhesive composition in the form of unreacted monomers. The composition of the monomer components constituting the adhesive composition is generally consistent with the composition of the monomer components of the photocrosslinkable adhesive formed from the adhesive composition and the composition of the monomer components constituting the photocrosslinked product thereof.

[0041] In this specification, the concept of "active energy rays" includes light such as ultraviolet rays, visible rays, and infrared rays, α rays, β rays, γ rays, electron rays, neutron beams, and radiation such as X-rays.

[0042] <Photo-crosslinkable adhesive>

[0043] According to the present specification, a photo-crosslinkable adhesive comprising a polymer having a benzophenone structure in a side chain (BP polymer) can be provided. The photo-crosslinkable adhesive meets at least one of the following conditions: being a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a component containing a benzophenone structure; having a VOC emission of 500 μg / g or less; and comprising two or more polymers having different monomer compositions, and at least one of the two or more polymers is the BP polymer.

[0044] (BP polymer)

[0045] As a preferred example of the BP polymer in the technology disclosed herein (including the BP polymer contained in the photocrosslinkable adhesive disclosed herein, and the BP polymer that can be used as a constituent component of the adhesive composition for producing the photocrosslinkable adhesive. The same below.), an acrylic polymer having a benzophenone structure in the side chain can be cited. The above-mentioned BP polymer may have an ethylenically unsaturated group or may not have an ethylenically unsaturated group. In some embodiments, the above-mentioned BP polymer is preferably a polymer that does not substantially contain an ethylenically unsaturated group.

[0046] In this specification, the so-called "benzophenone structure" refers to the general formula: Ar 1 -(C=O)-Ar 2 -, or -Ar 3 -(C=O)-Ar 2 Here, Ar in the above general formula is 1 is selected from phenyl groups which may have a substituent. 2 ,Ar 3 are each independently selected from a phenylene group which may have a substituent. 2 with Ar 3The above-mentioned benzophenone structure-containing component refers to a compound having at least one such benzophenone structure in the molecule. The benzophenone structure can be excited by ultraviolet irradiation and can capture hydrogen free radicals from other molecules or other parts of the molecule in its excited state.

[0047] The photo-crosslinkable adhesive disclosed herein comprises a polymer having a benzophenone structure in a side chain (BP polymer), and by exciting the benzophenone structure, a crosslinking structure can be formed by utilizing the hydrogen radical abstraction reaction. The polymer having a benzophenone structure in a side chain is preferably a polymer having the general formula: Ar 1 -(C=O)-Ar 2 -Ar in 1 is a phenyl group which may have a substituent, Ar 2 It is a polymer of a benzophenone structure of a phenylene group which may have a substituent. 1 and Ar 2 When at least one of the substituents has one or more substituents, the substituents can be independently selected from the group consisting of an alkoxy group (for example, an alkoxy group having 1 to 3 carbon atoms, preferably a methoxy group), a halogen atom (for example, F, Cl, Br, etc., preferably Cl or Br), a hydroxyl group, an amino group and a carboxyl group, but are not limited to these.

[0048] The BP polymer in the technology disclosed herein may be a polymer having a benzophenone structure as described above directly bonded to a side chain of the main chain, or may be a polymer having a benzophenone structure as described above bonded to a side chain of the main chain via one or more of, for example, an ester bond, an oxyalkylene structure, etc. As a preferred example of a BP polymer, a polymer comprising a repeating unit derived from an ethylenically unsaturated BP may be cited. The repeating unit may be a polymerized residue formed by reacting an ethylenically unsaturated group of a corresponding ethylenically unsaturated BP.

[0049] Examples of the ethylenically unsaturated BP include 4-acryloyloxybenzophenone, 4-acryloyloxy-4'-methoxybenzophenone, 4-acryloyloxyethoxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, and 2-hydroxy-4-acryloyloxybenzophenone, 4-[(2-acryloyloxy)ethoxy]benzophenone, 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone, and 4-methacryloyloxybenzophenone; 4-methacryloyloxybenzophenone, 4-methacryloyloxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, and 2-hydroxy-4-acryloyloxybenzophenone; 4-[(2-acryloyloxy)ethoxy]benzophenone, 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone, and 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone; and 4-[(2-acryloyloxy)ethoxy]-4'-bromobenzophenone. 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-bromobenzophenone, 2-hydroxy-4-methacryloyloxybenzophenone and the like may have substituted methacryloyloxybenzophenone; 4-[(2-methacryloyloxy)ethoxy]benzophenone, 4-[(2-methacryloyloxy)ethoxy]-4'-methoxybenzophenone and the like may have substituted methacryloyloxyalkoxybenzophenone; 4-vinylbenzophenone, 4'-bromo-3-vinylbenzophenone, 2-hydroxy-4-methoxy-4'-vinylbenzophenone and the like may have substituted vinylbenzophenone; etc., but are not limited to these. For ethylenically unsaturated BP, one alone or a combination of two or more may be used for the preparation of BP polymers. Ethylenically unsaturated BP may use commercially available products or may be synthesized by known methods. From the viewpoint of reactivity and the like, an ethylenically unsaturated BP having a (meth)acryloyl group, that is, an ethylenically unsaturated BP as an acrylic monomer can be preferably used.

[0050] The BP polymer may also be a copolymer having repeating units derived from ethylenically unsaturated BP and repeating units derived from ethylenically unsaturated compounds that are not ethylenically unsaturated BP (hereinafter, also referred to as "other monomers"). Such a BP polymer may be a copolymer of monomer components comprising the above-mentioned ethylenically unsaturated BP and the above-mentioned other monomers. In some embodiments, as the above-mentioned other monomers, one or more acrylic monomers may be preferably used. As a preferred example of a BP polymer, an acrylic BP polymer in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the monomer components constituting the BP polymer are acrylic monomers can be cited.

[0051] In some embodiments, the monomer components constituting the BP polymer may include one or more selected from (meth)acrylic acid alkyl esters having an alkyl group at the ester terminal as the above-mentioned other monomers. Hereinafter, (meth)acrylic acid alkyl esters having a linear or branched alkyl group with a carbon number of not less than X and not more than Y at the ester terminal are sometimes expressed as “(meth)acrylic acid CX-Y The monomer components constituting the BP polymer preferably contain at least (meth)acrylic acid C 1-20 As the other monomer, alkyl esters more preferably include (meth) acrylic acid C 4-20 As the other monomer, the alkyl ester further preferably contains (meth) acrylic acid C 4-18 Alkyl esters (e.g., acrylic acid C 4-9 Alkyl ester) as the above other monomer.

[0052] As (meth)acrylic acid C 1-20 Specific non-limiting examples of the alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like. As particularly preferred (meth) alkyl esters, n-butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), isononyl acrylate, etc. can be cited. As other specific examples of (meth) alkyl esters that can be preferably used, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA), etc. can be cited. The (meth) alkyl ester can be used alone or in combination of two or more. The monomer components constituting the BP polymer can also contain one or more selected from the copolymerizable monomers described later as the above-mentioned other monomers.

[0053] The photo-crosslinkable adhesive disclosed herein may be a photo-crosslinkable acrylic adhesive in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the total monomer components constituting the photo-crosslinkable adhesive are acrylic monomers. The photo-crosslinkable acrylic adhesive forms an acrylic photo-crosslinked product by photo-crosslinking. The photo-crosslinkable acrylic adhesive can be preferably used for optical purposes, for example, because its photo-crosslinked product can be a material with good transparency.

[0054] The weight average molecular weight (Mw) of the BP polymer is not particularly limited, and may be, for example, 0.5×10 4 ~500×10 4 From the viewpoint of the cohesiveness of the photo-crosslinkable adhesive, the handleability of the adhesive sheet having the photo-crosslinkable adhesive, etc., in some embodiments, the Mw of the BP polymer is usually 1×10 4 The above is appropriate, preferably 5×10 4 Above, it can be 10×10 4 Above, it can be 15×10 4 Above, it can be 20×10 4 In addition, from the viewpoint of the surface shape conformability of the photo-crosslinkable adhesive to the adherend (for example, an optical member), the Mw of the BP polymer contained in the photo-crosslinkable adhesive is usually 200×10 4 The following are suitable, preferably 150×10 4 Below, it can be 100×10 4 Below, it can be 70×10 4 Below, it can be 50×10 4 In some embodiments, the Mw of the BP polymer may be 40×10 4 Below, it can be 30×10 4 Below, it can be 25×10 4 Below, it can be 20×10 4 the following.

[0055] It should be noted that, in this specification, the weight average molecular weight (Mw) of a polymer refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (column: TSKgelGMH-H (S), manufactured by TOSOH) can be used.

[0056] In the technology disclosed herein, the glass transition temperature (Tg) of the BP polymer is not particularly limited. The Tg of the BP polymer may be, for example, from -80°C to 150°C, from -80°C to 50°C, or from -80°C to 10°C. From the viewpoint of the surface shape followability of the photo-crosslinkable adhesive, in some embodiments, it is appropriate that the Tg of the BP polymer is lower than 0°C, preferably below -10°C, below -20°C, below -30°C, below -35°C, below -40°C, or below -50°C. In addition, from the viewpoint of the cohesion of the photo-crosslinkable adhesive and the deformation resistance after photo-crosslinking (for example, the durability of adhesion to the adherend), it is generally advantageous for the Tg of the BP polymer to be above -75°C, above -70°C, or above -65°C. In some embodiments, the Tg of the BP polymer may be above -55°C, above -45°C, or above -40°C. The Tg of the BP polymer can be adjusted by the types and amounts of the monomer components constituting the BP polymer.

[0057] Here, in this specification, the glass transition temperature (Tg) of a polymer refers to the glass transition temperature obtained by the Fox formula based on the composition of the monomer components constituting the polymer. As shown below, the above Fox formula is a relationship between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each monomer constituting the copolymer.

[0058] 1 / Tg=Σ(Wi / Tgi)

[0059] It should be noted that, in the above Fox formula, Tg represents the glass transition temperature of the copolymer (unit: K), Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio based on weight), and Tgi represents the glass transition temperature of the homopolymer of monomer i (unit: K).

[0060] As the glass transition temperature of the homopolymer used for calculation of Tg, the value described in the known document is used. For example, regarding the monomers listed below, as the glass transition temperature of the homopolymer of the monomer, the following value is used.

[0061]

[0062]

[0063] Regarding the glass transition temperature of homopolymers of monomers other than those exemplified above, the values ​​recorded in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) are used. When multiple values ​​are recorded in the document, the highest value is adopted. Regarding monomers whose homopolymer glass transition temperatures are not recorded in the above-mentioned Polymer Handbook, the values ​​obtained by the measurement method described in Japanese Patent Application Publication No. 2007-51271 are used. It should be noted that for polymers for which a nominal value of the glass transition temperature is provided by a manufacturer, the nominal value can be adopted.

[0064] For the BP polymer in the technology disclosed herein, it is preferred that the BP polymer contains, for example, about 0.5 mg or more of benzophenone structure in terms of 4-benzoylphenyl acrylate per 1 g of the polymer. Hereinafter, the value obtained by converting the number of benzophenone structures contained in 1 g of the BP polymer into the amount converted in terms of 4-benzoylphenyl acrylate is sometimes referred to as the BP equivalent of the BP polymer (unit: mg / g). For example, in the case where 40 μmol of benzophenone structure is contained in 1 g, the BP equivalent of the polymer is calculated to be 10 mg / g.

[0065] From the perspective of obtaining a higher photocrosslinking effect (for example, the effect of improving deformation resistance by photocrosslinking), in some embodiments, the BP equivalent of the BP polymer is usually 1 mg / g or more, preferably 1.5 mg / g or more, for example, 2 mg / g or more, 5 mg / g or more, 8 mg / g or more, 10 mg / g or more, 15 mg / g or more, or 20 mg / g or more. In addition, in some embodiments, from the perspective of improving the impact resistance and peel strength of the joint formed by the photocrosslinked product, the BP equivalent of the BP polymer is usually 100 mg / g or less, 80 mg / g or less, 60 mg / g or less, 40 mg / g or less, 25 mg / g or less, or 15 mg / g or less. In some embodiments, the BP equivalent of the BP polymer may be lower than 10 mg / g, or lower than 5 mg / g. The BP equivalent of the BP polymer can be adjusted by the composition of the monomer components constituting the BP polymer.

[0066] The weight ratio of the BP polymer in the photocrosslinkable adhesive as a whole, i.e., the weight fraction of the BP polymer in the photocrosslinkable adhesive, is not particularly limited and can be set in a manner that is ideally balanced between the surface shape followability of the photocrosslinkable adhesive and the deformation resistance of its photocrosslinked product. In some embodiments, the weight fraction of the BP polymer can be, for example, 1% by weight or more, and 5% by weight or more is usually appropriate, and can be 10% by weight or more, 15% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 45% by weight or more, 50% by weight or more, or 55% by weight or more. If the weight fraction of the BP polymer increases, there is a tendency for the ΔG' described later to increase. The technology disclosed herein can also be implemented in a manner in which the weight fraction of the BP polymer in the photocrosslinkable adhesive is substantially 100% by weight (e.g., 99.5% by weight or more). In addition, from the perspective of the adjustability of adhesive performance and the ease of VOC reduction, in some embodiments, the weight fraction of the BP polymer in the photo-crosslinkable adhesive can be, for example, lower than 99 weight %, lower than 95 weight %, lower than 85 weight %, lower than 70 weight %, lower than 60 weight %, lower than 50 weight %, lower than 40 weight %, or lower than 35 weight %.

[0067] For the photo-crosslinkable adhesive disclosed herein, it is preferred that about 0.1 mg or more of benzophenone structure is contained in 1 g of the photo-crosslinkable adhesive in terms of 4-benzoylphenyl acrylate. Hereinafter, the weight of benzophenone structure contained in 1 g of the photo-crosslinkable adhesive in terms of 4-benzoylphenyl acrylate is sometimes referred to as the BP equivalent of the photo-crosslinkable adhesive (unit: mg / g). From the viewpoint of obtaining a higher photo-crosslinking effect (for example, the effect of improving deformation resistance by photo-crosslinking), in some embodiments, the BP equivalent of the photo-crosslinkable adhesive is generally appropriate to be 0.3 mg / g or more, and may be 0.5 mg / g or more, 1 mg / g or more, 5 mg / g or more, 10 mg / g or more, or 20 mg / g or more. In addition, in some embodiments, from the perspective of impact resistance of the joint formed by the photocrosslinked product and strain suppression within the photocrosslinked product, the BP equivalent of the photocrosslinkable adhesive is generally appropriate to be 100 mg / g or less, and can be 80 mg / g or less, 60 mg / g or less, 40 mg / g or less, 25 mg / g or less, or 15 mg / g or less.

[0068] The photo-crosslinkable adhesive disclosed herein may be a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a benzophenone-containing structural component. For the above-mentioned adhesive composition, as the above-mentioned benzophenone-containing structural component, it may include one or more monomers selected from the above-mentioned ethylenically unsaturated BP, it may also include a pre-synthesized BP polymer, or it may include both. The BP polymer contained in the above-mentioned photo-crosslinkable adhesive may be, for example, the BP polymer contained in the above-mentioned adhesive composition or a modified product thereof, or it may be a polymer formed by copolymerization of the ethylenically unsaturated BP contained in the above-mentioned adhesive composition with other monomers.

[0069] The photocrosslinkable adhesive disclosed herein may be a photocrosslinkable adhesive comprising two or more polymers with different monomer compositions, and at least one of the two or more polymers is the BP polymer. For the photocrosslinkable adhesive, as the two or more polymers, only two or more BP polymers may be included, or a combination of a polymer not having a benzophenone structure (hereinafter also referred to as a "non-BP polymer") and a BP polymer may be included. The non-BP polymer may be formed, for example, by using an adhesive composition comprising an ethylenically unsaturated compound not having a benzophenone structure and polymerizing the ethylenically unsaturated compound. From the viewpoint of compatibility, etc., the BP polymer and the non-BP polymer are preferably both acrylic polymers.

[0070] The two or more polymers may be chemically bonded or not. Some embodiments of the photo-crosslinkable adhesive may include at least one BP polymer in a form that is not chemically bonded to a polymer other than the BP polymer. The photo-crosslinkable adhesive may form a photo-crosslinked product in which the BP polymer is chemically bonded to a polymer other than the BP polymer by photo-crosslinking the benzophenone structure of the BP polymer.

[0071] The photo-crosslinkable adhesive disclosed herein may contain other components useful for an adhesive as needed. A photo-crosslinkable adhesive containing such optional components may be formed using an adhesive composition having a corresponding composition.

[0072] (VOC emission)

[0073] The VOC emission of the photocrosslinkable adhesive disclosed herein is not particularly limited. The above-mentioned VOC emission can be, for example, less than 5000 μg / g, less than 3000 μg / g, or less than 1000 μg / g. In some embodiments, the VOC emission of the photocrosslinkable adhesive is preferably less than 500 μg / g, more preferably less than 300 μg / g, and further preferably less than 100 μg / g. Photocrosslinkable adhesives with low VOC emission are low in odor and are preferred from the perspective of environmental hygiene. Low VOC emission of the photocrosslinkable adhesive is also preferred from the perspective of suppressing foaming caused by volatile organic compounds (VOCs) in the photocrosslinkable adhesive and low pollution. For the VOC emission of the photocrosslinkable adhesive, an appropriate amount of the photocrosslinkable adhesive (for example, about 1 mg to 2 mg) can be used as a measurement sample and measured by the following method. It should be noted that the thickness of the measurement sample is preferably less than 1 mm.

[0074] [VOC measurement test]

[0075] The test sample is placed in a 20 mL vial and covered tightly. Next, the vial is heated at 80°C for 30 minutes, and 1.0 mL of the heated gas (sample gas) is injected into a gas chromatography (GC) measuring device using a headspace autosampler (HSS). Based on the obtained gas chromatogram, the amount of gas generated by the test sample is calculated in the form of an amount converted to n-decane. The VOC emission amount (μg / g) per 1 g of the test sample is calculated from the obtained value. It should be noted that the amount converted to n-decane is calculated by treating the detection intensity of the generated gas obtained by GCMass as the detection intensity of n-decane and applying a pre-made standard curve for n-decane. The settings of HSS and GC are as follows.

[0076] HSS: Model "7694" manufactured by Agilent Technologies

[0077] Heating time: 30 minutes

[0078] Pressurization time: 0.12 minutes

[0079] Loop filling time: 0.12 minutes

[0080] Ring equilibration time: 0.05 minutes

[0081] Injection time: 3 minutes

[0082] Sample ring temperature: 160°C

[0083] Transmission line temperature: 200°C

[0084] GC device: Model "6890" manufactured by Agilent Technologies

[0085] Column: J&W capillary column manufactured by GL Science, trade name "DB-WAP" (inner diameter 0.533 mm × length 30 m, film thickness 1.0 μm)

[0086] Column temperature: 250°C (increase temperature from 40°C to 90°C at 10°C / min, then continue to increase temperature to 250°C at 20°C / min and maintain for 5 minutes)

[0087] Column pressure: 24.3kPa (constant flow mode)

[0088] Carrier gas: Helium (5.0mL / min)

[0089] Inlet: split (split ratio is 12:1)

[0090] Inlet temperature: 250℃

[0091] Detector: FID

[0092] Detector temperature: 250°C

[0093] Generally, volatile organic compounds that are important factors that may increase the VOC emission of adhesives include organic solvents (e.g., residues of organic solvents contained in the adhesive composition used in the preparation of the photocrosslinkable adhesive), unreacted products of ethylenically unsaturated compounds contained in the adhesive composition (e.g., unpolymerized acrylic monomers. Hereinafter, also referred to as "residual monomers"), etc. The photocrosslinkable adhesive disclosed herein may be a photocrosslinkable adhesive in which the content of such organic solvents and residual monomers is suppressed to a level that satisfies any of the above-mentioned VOC emission amounts. The photocrosslinkable adhesive disclosed herein has a structure in which the amount of residual monomers is limited as described above, and can form new crosslinks in the system by utilizing the benzophenone structure of the BP polymer, thereby forming a photocrosslinked product with improved deformation resistance.

[0094] It should be noted that the VOC emission of the photo-crosslinkable adhesive disclosed in this article is preferably as low as possible in principle, but from practical viewpoints such as productivity and cost, in some embodiments, the above-mentioned VOC emission can be, for example, 10 μg / g or more, 30 μg / g or more, 80 μg / g or more, 150 μg / g or more, or 200 μg / g or more.

[0095] (Shear storage elastic modulus)

[0096] In the technology disclosed herein, the shear storage elastic modulus Ga' [kPa] of the photocrosslinkable adhesive at 30°C is not particularly limited. It is preferred that the shear storage elastic modulus Ga' [kPa] of the photocrosslinkable adhesive at 30°C is generally higher than 1 kPa. Hereinafter, the above-mentioned shear storage elastic modulus Ga' is sometimes referred to as "room temperature elastic modulus Ga' before photocrosslinking" or simply "room temperature elastic modulus Ga'". From the viewpoints of the cohesiveness of the photocrosslinkable adhesive, the operability (e.g., processability) of an adhesive sheet having an adhesive layer formed by the photocrosslinkable adhesive, etc., the room temperature elastic modulus Ga' is preferably higher than 5 kPa, more preferably higher than 10 kPa, may be higher than 15 kPa, may be higher than 25 kPa, and may be higher than 30 kPa. In some embodiments, the room temperature elastic modulus Ga' may be higher than 50 kPa, may be higher than 65 kPa, and may be higher than 75 kPa. In view of the conformability to the surface shape of the adherend, the room temperature elastic modulus Ga' is usually 500 kPa or less, preferably 200 kPa or less, and may be 100 kPa or less. In some embodiments, the room temperature elastic modulus Ga' may be less than 80 kPa, and may be less than 60 kPa.

[0097] The room temperature elastic modulus Ga' of the photocrosslinkable adhesive can be obtained by measuring the dynamic viscoelasticity under the same conditions as the elastic modulus Gb' before photocrosslinking described in the examples below. The room temperature elastic modulus Ga' can be adjusted by the composition of the photocrosslinkable adhesive (e.g., BP equivalent weight, Mw of BP polymer, composition of monomer components constituting BP polymer, weight fraction of BP polymer), etc.

[0098] The shear storage elastic modulus of the photocrosslinkable adhesive at 80°C (i.e., the elastic modulus Gb' before photocrosslinking) is not particularly limited. From the viewpoints of the cohesion of the photocrosslinkable adhesive, the operability of the adhesive sheet having the photocrosslinkable adhesive (e.g., the storage property of the adhesive sheet), it is appropriate that the elastic modulus Gb' is generally higher than 3kPa, preferably higher than 5kPa, more preferably higher than 10kPa, and may be higher than 15kPa. In some embodiments, from the viewpoints of the processability of the adhesive sheet having the photocrosslinkable adhesive, the elastic modulus Gb' may be higher than 30kPa, higher than 40kPa, higher than 50kPa, and higher than 52kPa. The photocrosslinkable adhesive having the elastic modulus Gb' may be preferably used as a constituent element of an adhesive layer having a thickness greater than 50μm, greater than 70μm, or greater than 90μm formed by the photocrosslinkable adhesive, or an adhesive sheet having the adhesive layer.

[0099] The elastic modulus Gb' can be measured by the method described in the examples below. The elastic modulus Gb' can be adjusted by the composition of the photo-crosslinkable adhesive (eg, BP equivalent weight, Mw of BP polymer, composition of monomer components constituting BP polymer, weight fraction of BP polymer).

[0100] Use a high pressure mercury lamp with an illumination of 300mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The conditions for the shear storage elastic modulus Gc' [kPa] at 80°C of the photocrosslinked product obtained by irradiating the photocrosslinkable adhesive with ultraviolet rays (i.e., the elastic modulus Gc' after photocrosslinking) are not particularly limited. From the viewpoint of suppressing the cohesive failure of the joint formed by the photocrosslinked product, it is generally advantageous for the elastic modulus Gc' to be 15 kPa or more, preferably 25 kPa or more. From the viewpoint of improving the durability of the close fit to the adherend (especially the adherend that is prone to outgassing, such as polarizing plates), it is advantageous for the elastic modulus Gc' to be 30 kPa or more, preferably 35 kPa or more, and more preferably 40 kPa or more. In some embodiments, the elastic modulus Gc' may be 45 kPa or more, 50 kPa or more, 55 kPa or more, or 60 kPa or more. In addition, the elastic modulus Gc' may be, for example, 200 kPa or less, 150 kPa or less, or 120 kPa or less. From the perspective of achieving good balance between adhesion durability and other properties (such as peel strength) to the adherend, it is advantageous for the elastic modulus Gc' to be less than 100 kPa, preferably less than 80 kPa, less than 70 kPa, or less than 65 kPa. If the elastic modulus Gc' is lowered, there is a tendency that the peel strength of the photo-crosslinked product formed by laminating the photo-crosslinkable adhesive on the adherend and photo-crosslinking the photo-crosslinked adhesive from the adherend is substantially improved. In some embodiments, the elastic modulus Gc' may be less than 60 kPa, less than 55 kPa, less than 50 kPa, or less than 45 kPa.

[0101] More specifically, the elastic modulus Gc' can be measured by the method described in the examples below. The elastic modulus Gc' can be adjusted by the composition of the photocrosslinkable adhesive (e.g., BP equivalent weight, Mw of BP polymer, composition of monomer components constituting BP polymer, weight fraction of BP polymer).

[0102] The relationship between the elastic modulus Gb' of the photocrosslinkable adhesive and the elastic modulus Gc' of its photocrosslinked product is not particularly limited, but typically satisfies Gc'[kPa]-Gb'[kPa]>0[kPa]. ΔG' may be, for example, 0.5 kPa or more, preferably 1 kPa or more, and more preferably 2 kPa or more. In a photocrosslinkable adhesive having a ΔG' of 2 kPa or more, it is easy and appropriate to exert the effect of improving deformation resistance brought about by photocrosslinking. From the viewpoint of obtaining a higher photocrosslinking effect, in some embodiments, ΔG' may be 3 kPa or more, may be 5 kPa or more, for example, preferably 8 kPa or more, may be 10 kPa or more, may be 15 kPa or more, may be 20 kPa or more, may be 25 kPa or more, and may be 30 kPa or more. There is no particular upper limit on ΔG', but from the viewpoint of achieving both surface shape followability when attached to an adherend and deformation resistance after photocrosslinking in a well-balanced manner, it is usually appropriate to be 150 kPa or less, preferably 100 kPa or less, and may be 80 kPa or less, 65 kPa or less, 50 kPa or less, or 40 kPa or less.

[0103] (Gel fraction)

[0104] The gel fraction of the photo-crosslinkable adhesive disclosed herein is not particularly limited, but from the viewpoints of the cohesiveness of the photo-crosslinkable adhesive, the operability of the adhesive sheet having the adhesive layer formed by the photo-crosslinkable adhesive, etc., it is usually appropriate to be 5% or more, preferably 15% or more, 25% or more, or 35% or more. The gel fraction of the photo-crosslinkable adhesive is in principle 100% or less. In addition, from the viewpoint of the ability to follow the surface shape of the adherend, the gel fraction of the photo-crosslinkable adhesive is preferably less than 85%, less than 70%, less than 55%, or less than 40%.

[0105] The gel fraction can be measured by the following method. That is, about 0.5 g of the sample is accurately weighed and its weight is referred to as W1. The sample is wrapped in a porous PTFE (polytetrafluoroethylene) sheet, immersed in ethyl acetate at room temperature for 1 week, and then dried. The weight W2 of the component insoluble in ethyl acetate is measured, and W1 and W2 are substituted into the following formula to calculate the gel fraction.

[0106] Gel fraction (%) = W2 / W1×100

[0107] As the porous PTFE sheet, a product of Nitto Denko Corporation, trade name "NITOFLON NTF1122" or an equivalent product thereof can be used.

[0108] In some embodiments of the photo-crosslinkable adhesive disclosed herein, a high pressure mercury lamp is used with an illumination of 300 mW / cm2 、Accumulated light intensity 10000mJ / cm 2 The gel fraction of the photocrosslinked product obtained by irradiating the photocrosslinkable adhesive with ultraviolet rays can be, for example, 70% or more, preferably 90% or more, 95% or more, or 98% or more. The gel fraction of the photocrosslinked product is in principle 100% or less. The gel fraction can be measured by the above method.

[0109] (Formation of Photocrosslinked Product)

[0110] For the photo-crosslinkable adhesive disclosed herein, for example, photo-crosslinking can be performed by irradiating ultraviolet rays containing wavelength components that can excite the benzophenone structure. It is preferred to use a light source that can irradiate ultraviolet rays containing components with a wavelength lower than 300 nm. Examples of the light source include high-pressure mercury lamps, low-pressure mercury lamps, metal halide lamps, and ultra-UV lamps, but are not limited to these. The light irradiated by the above light source may also contain components with a wavelength of more than 300 nm.

[0111] It should be noted that as a light source that can irradiate ultraviolet rays that do not contain a wavelength component (for example, a component with a wavelength lower than 300 nm) that can excite a benzophenone structure or a small amount of such a wavelength component, a black light lamp, a UV-LED lamp, etc. can be cited. These light sources can be preferably used as a light source for causing a reaction (polymerization reaction or curing reaction) of an ethylenically unsaturated group by light irradiation performed in the presence of a benzophenone structure. In the ultraviolet irradiation for causing an ethylenically unsaturated group to react, a photoinitiator described later can be used to promote the reaction.

[0112] The photocrosslinkable adhesive disclosed herein may be a composition that is substantially free of a photoinitiator that generates free radicals by absorbing light with a wavelength of more than 300 nm, for example, it may be a composition that is substantially free of a photoinitiator that generates free radicals by absorbing visible light of more than 380 nm (especially more than 400 nm). This is advantageous from the perspective of the optical properties of the photocrosslinkable adhesive. It should be noted that the so-called photoinitiator that does not generate free radicals by absorbing light with a wavelength of more than 300 nm refers to the above-mentioned photoinitiator that does not contain the above-mentioned form that can generate free radicals (the above-mentioned form with a site that is cleaved under the action of light), and the cleavage residue of the above-mentioned photoinitiator may be allowed. A preferred embodiment involves a photocrosslinkable adhesive that is substantially free of a photoinitiator that contains a phosphorus element in the molecule. The photocrosslinkable adhesive disclosed herein may be a photocrosslinkable adhesive that is substantially free of a photoinitiator that contains a phosphorus element in the molecule and any substance in the cleavage residue of the photoinitiator.

[0113] <Adhesive composition>

[0114] According to the present specification, an adhesive composition comprising a polymer (BP polymer) (A) having a benzophenone structure in a side chain and an ethylenically unsaturated compound (B) can be provided. The adhesive composition can be used to manufacture any photo-crosslinkable adhesive disclosed herein. In some embodiments, the adhesive composition can be an acrylic adhesive composition in which more than 50% by weight (preferably more than 70% by weight, for example more than 90% by weight) of the total monomer components constituting the adhesive composition are acrylic monomers.

[0115] As the BP polymer (A) that can be used as a constituent component of the adhesive composition, the same polymer as the BP polymer contained in the photo-crosslinkable adhesive can be used, and therefore, repeated description is omitted.

[0116] (Ethylenically unsaturated compound (B))

[0117] Examples of compounds that can be used as the ethylenically unsaturated compound (B) include the above-mentioned alkyl (meth)acrylates and the above-mentioned ethylenically unsaturated BPs. Among these, it is preferred to use at least an alkyl (meth)acrylate (e.g., C (meth)acrylate). 1-20 Alkyl ester, more preferably (meth) acrylic acid C 4-18 Alkyl ester, more preferably acrylic acid C 4-9 As particularly preferred (meth)acrylic acid alkyl esters, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) can be cited. As other specific examples of (meth)acrylic acid alkyl esters that can be preferably used, isononyl acrylate, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (iSTA) and the like can be cited. (Meth)acrylic acid alkyl esters can be used alone or in combination of two or more. In some embodiments, the ethylenically unsaturated compound (B) preferably includes any one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA). In one embodiment, it is more preferred to include at least 2EHA. In another embodiment, it is more preferred to include at least BA.

[0118] In some embodiments, the ethylenically unsaturated compound (B) may contain acrylic acid C in a ratio of 40 wt % or more. 4-9 Alkyl esters. Acrylic acid C 4-9 The proportion of the alkyl ester in the ethylenically unsaturated compound (B) may be, for example, 50% by weight or more, 60% by weight or more, or 65% by weight or more. In addition, from the viewpoint of improving the cohesiveness of the photo-crosslinkable adhesive, the acrylic acid C 4-9The proportion of the alkyl ester in the ethylenically unsaturated compound (B) is usually appropriately 99.5% by weight or less, and may be 95% by weight or less, 85% by weight or less, 70% by weight or less, or 60% by weight or less.

[0119] As other examples of compounds that can be used as ethylenically unsaturated compounds (B), ethylenically unsaturated compounds (copolymerizable monomers) that can copolymerize with (meth) alkyl acrylates can be cited. As copolymerizable monomers, monomers having polar groups (e.g., carboxyl groups, hydroxyl groups, rings containing nitrogen atoms, etc.) can be preferably used. Monomers having polar groups can help, for example, to introduce crosslinking points into a polymer containing repeating units derived from the monomer, or to improve the cohesive force of a photocrosslinkable adhesive. Copolymerizable monomers can be used alone or in combination of two or more.

[0120] Specific non-limiting examples of the copolymerizable monomer include the following monomers.

[0121] Monomers containing a carboxyl group: for example, acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like.

[0122] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.

[0123] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0124] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0125] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl (meth)acrylate ether, allyl glycidyl ether, and glycidyl (meth)acrylate ether.

[0126] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.

[0127] Monomers containing an isocyanate group: for example, 2-(meth)acryloyloxyethyl isocyanate, (meth)acryloyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, and the like.

[0128] Monomers containing amide groups: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and other N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and other N-alkyl (meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinyl acetamide; monomers having hydroxyl groups and amide groups, such as N-(2-hydroxyethyl) ( N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide and the like; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl(meth)acrylamide, such as N-methoxymethyl(meth)acrylamide, N-methoxyethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide; and N,N-dimethylaminopropyl(meth)acrylamide, N-(meth)acrylamide and the like.

[0129] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0130] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0131] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-(meth)acryloylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam).

[0132] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.

[0133] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.

[0134] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.

[0135] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0136] Alkoxy group-containing monomers: for example, alkoxyalkyl (meth)acrylates (alkoxyalkyl (meth)acrylates) such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; and alkoxyalkylene (meth)acrylates (for example, alkoxypolyalkylene glycol (meth)acrylate) such as methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.

[0137] Monomers containing alkoxysilyl groups: for example, (meth)acrylates containing alkoxysilyl groups such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, and the like; and vinyl compounds containing alkoxysilyl groups such as vinyltrimethoxysilane and vinyltriethoxysilane.

[0138] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.

[0139] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0140] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0141] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.

[0142] (Meth)acrylates having an alicyclic hydrocarbon group: for example, (meth)acrylates having an alicyclic hydrocarbon group such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, and adamantyl (meth)acrylate.

[0143] (Meth)acrylates having an aromatic hydrocarbon group: for example, (meth)acrylates having an aromatic hydrocarbon group, such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate.

[0144] In addition, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates containing halogen atoms such as (meth)acrylates containing vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as silicone (meth)acrylate, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0145] When using such a copolymerizable monomer, its usage amount is not particularly limited, and it is usually appropriate to be more than 0.01% by weight of the overall monomer component constituting the adhesive composition. From the viewpoint of better exerting the use effect of the copolymerizable monomer, the usage amount of the copolymerizable monomer (that is, the weight fraction of the copolymerizable monomer in the above-mentioned overall monomer component) can be more than 0.1% by weight of the overall monomer component, and can be more than 0.5% by weight. In addition, from the viewpoint of easily obtaining the balance of adhesive properties, it is appropriate that the usage amount of the copolymerizable monomer is usually less than 50% by weight of the overall monomer component, preferably less than 40% by weight.

[0146] In some embodiments, the copolymerizable monomer may include a monomer having a nitrogen atom. By using a monomer having a nitrogen atom, the cohesive force of the photocrosslinkable adhesive can be increased, and the peel strength after photocrosslinking can be ideally increased. As a preferred example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a ring containing a nitrogen atom, the monomers exemplified above can be used, for example, N-vinyl cyclic amide represented by general formula (1) can be used.

[0147] [Chemical formula 1]

[0148]

[0149] Here, in the general formula (1), R 1 is a divalent organic group, specifically -(CH2) n -. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone can be preferably used. Another preferred example of the monomer having a nitrogen atom is (meth)acrylamide.

[0150] There is no particular restriction on the amount of monomers with nitrogen atoms (preferably monomers with rings containing nitrogen atoms such as N-vinyl cyclic amides, N-(methyl)acryloyl cyclic amides, etc.), for example, it can be more than 1% by weight of the entire monomer component, it can be more than 2% by weight, it can be more than 3% by weight, and further can be more than 5% by weight or more than 7% by weight. In one embodiment, the amount of monomers with nitrogen atoms can be more than 10% by weight of the entire monomer component, it can be more than 15% by weight, or it can be more than 20% by weight. In addition, it is appropriate that the amount of monomers with nitrogen atoms is less than 40% by weight of the entire monomer component, it can be less than 35% by weight, it can be less than 30% by weight, or it can be less than 25% by weight. In another embodiment, the amount of monomers with nitrogen atoms can be less than 20% by weight of the entire monomer component, it can be less than 15% by weight, it can be less than 10% by weight or less than 6% by weight.

[0151] In some ways, the copolymerizable monomer may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesive force of the photo-crosslinkable adhesive and the degree of crosslinking (for example, crosslinking based on an isocyanate crosslinking agent) can be appropriately adjusted. The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the entire monomer component, it can be more than 0.1% by weight, it can be more than 0.5% by weight, it can be more than 1% by weight, it can be more than 5% by weight or more than 10% by weight. In addition, from the viewpoint of suppressing the water absorption of the photo-crosslinkable adhesive or its photo-crosslinked product, in some ways, the amount of the monomer containing a hydroxyl group is appropriate for the overall monomer component, for example, less than 40% by weight, it can be less than 30% by weight, it can be less than 25% by weight, it can be less than 20% by weight. In another way, the amount of the monomer containing a hydroxyl group can be less than 15% by weight of the entire monomer component, it can be less than 10% by weight, it can be less than 5% by weight. Alternatively, as the copolymerizable monomer, a monomer containing a hydroxyl group may not be used.

[0152] In some embodiments, the proportion of carboxyl-containing monomers in the overall monomer composition can be, for example, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight (e.g., less than 0.1% by weight). The adhesive composition may not substantially contain carboxyl-containing monomers as its constituent monomer components. Here, the so-called substantially not containing carboxyl-containing monomers means that carboxyl-containing monomers are at least not intentionally used. This will become advantageous from the perspective of the metal corrosion resistance of the photocrosslinkable adhesive formed by the adhesive composition and its photocrosslinked product.

[0153] In some embodiments, the copolymerizable monomer may include a (meth) acrylate containing an alicyclic hydrocarbon group. Thus, the cohesive force of the adhesive can be increased, and the peel strength after photocrosslinking can be increased. As a (meth) acrylate containing an alicyclic hydrocarbon group, the (meth) acrylate containing an alicyclic hydrocarbon group exemplified above can be used, for example, cyclohexyl acrylate and isobornyl acrylate can be preferably used. The amount used when using a (meth) acrylate containing an alicyclic hydrocarbon group is not particularly limited, for example, it can be more than 1% by weight, more than 3% by weight, or more than 5% by weight of the overall monomer component. In one embodiment, the amount of (meth) acrylate containing an alicyclic hydrocarbon group can be more than 10% by weight of the overall monomer component, can be more than 15% by weight, can be higher than 20% by weight, and can be higher than 25% by weight. It is appropriate that the upper limit of the amount of (meth) acrylate containing an alicyclic hydrocarbon group is about 40% by weight or less, for example, it can be less than 30% by weight, and can be less than 25% by weight (for example, less than 15% by weight, and further less than 10% by weight).

[0154] In some embodiments, the copolymerizable monomer may include a monomer containing an alkoxysilyl group. The monomer containing an alkoxysilyl group is typically an ethylenically unsaturated compound having at least one (preferably more than two, for example, two or three) alkoxysilyl group in one molecule, and its specific example is as described above. The above-mentioned monomer containing an alkoxysilyl group can be used alone or in combination of two or more. By using a monomer containing an alkoxysilyl group, a cross-linked structure formed by a condensation reaction of a silanol group (silanol condensation) can be introduced into a photo-crosslinkable adhesive. The monomer containing an alkoxysilyl group can also help to improve the peel strength for the adherend.

[0155] The amount used in the case of using a monomer containing an alkoxysilyl group is not particularly limited. In some embodiments, the amount of the monomer containing an alkoxysilyl group can be, for example, 0.005% by weight or more of the overall monomer component constituting the adhesive composition, and it is usually appropriate to be 0.01% by weight or more, and it can be 0.03% by weight or more, and it can be 0.05% by weight or more, and it can be 0.07% by weight or more, and from the viewpoint of obtaining a higher effect of use, it can be higher than 0.1% by weight, and it can be higher than 0.2% by weight or higher than 0.3% by weight. In addition, from the viewpoint of the surface shape followability of the photocrosslinkable adhesive, the amount of the monomer containing an alkoxysilyl group is usually appropriate to be less than 1.0% by weight of the overall monomer component, and it can be less than 0.5% by weight, and it can be less than 0.35% by weight, and it can be less than 0.25% by weight, and it can be less than 0.1% by weight, and it can be less than 0.1% by weight.

[0156] As other examples of compounds that can be used as the ethylenically unsaturated compound (B), a multifunctional monomer can be cited. According to the adhesive composition containing the multifunctional monomer, by reacting the multifunctional monomer when curing the composition to produce a photo-crosslinkable adhesive, a photo-crosslinkable adhesive formed by crosslinking the multifunctional monomer can be obtained.

[0157] Examples of the polyfunctional monomer include bifunctional monomers such as 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, and divinylbenzene; polyfunctional monomers having three or more functionalities such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; and epoxy acrylates, polyester acrylates, and urethane acrylates. Among them, preferred examples include 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. The polyfunctional monomer may be used alone or in combination of two or more.

[0158] The amount used in the case of using a multifunctional monomer is not particularly limited, and can be set in a manner that forms a photo-crosslinkable adhesive that exerts ideal characteristics in a photo-crosslinkable adhesive. In some ways, the amount of the multifunctional monomer used can be less than 5.0% by weight of the overall monomer component constituting the adhesive composition. Thus, it is possible to avoid forming an excessive crosslinked structure during the formation of the photo-crosslinkable adhesive (i.e., in the stage before photo-crosslinking), thereby improving the surface shape followability of the photo-crosslinkable adhesive. The amount of the above-mentioned multifunctional monomer used, for example, can be less than 4.0% by weight of the overall monomer component, can be less than 3.0% by weight, can be less than 2.0% by weight, can be less than 1.0% by weight, can be less than 0.5% by weight, can be less than 0.3% by weight. It is also possible not to use a multifunctional monomer. In addition, in some ways, from the perspective of imparting appropriate agglomeration to the photo-crosslinkable adhesive, the amount of the multifunctional monomer used relative to the overall monomer component can be, for example, more than 0.001% by weight, can be more than 0.005% by weight, can be more than 0.01% by weight, can be more than 0.03% by weight.

[0159] From the viewpoint of the surface shape following property of the photo-crosslinkable adhesive, in some embodiments, a bifunctional monomer may be preferably used as the multifunctional monomer. The proportion of the bifunctional monomer in the overall multifunctional monomer used may be, for example, 50% by weight or more, 70% by weight or more, 90% by weight or more, or 100% by weight.

[0160] The weight ratio of the BP polymer (A) contained in the adhesive composition to the total amount of the BP polymer (A) and the ethylenically unsaturated compound (B) is not particularly limited, and can be set in a manner that the surface shape followability of the photo-crosslinkable adhesive formed by the adhesive composition and the deformation resistance of its photo-crosslinked product are ideally balanced. In some embodiments, the weight fraction of the above-mentioned BP polymer can be, for example, 1% by weight or more, and it is usually appropriate to be 5% by weight or more. From the perspective of improving the effect of photo-crosslinking, it can be 10% by weight or more, 15% by weight or more, 25% by weight or more, 35% by weight or more, 45% by weight or more, or 55% by weight or more. In addition, from the perspective of ease of preparation and coating of the adhesive composition, in some embodiments, the weight ratio of the BP polymer in the above-mentioned total amount can be, for example, less than 99% by weight, less than 95% by weight, less than 85% by weight, less than 70% by weight, less than 50% by weight, or less than 40% by weight.

[0161] In the adhesive composition disclosed herein, the weight of the organic solvent in the overall weight of the adhesive composition can be, for example, less than 30% by weight, and less than 20% by weight is advantageous, preferably less than 10% by weight, and more preferably less than 5% by weight. In some embodiments, the weight ratio of the above-mentioned organic solvent can be less than 3% by weight, less than 1% by weight, less than 0.5% by weight, less than 0.1% by weight, less than 0.05% by weight, or substantially free of organic solvent. From the perspective of reducing the VOC of the photo-crosslinkable adhesive formed by the adhesive composition, it is preferred to suppress the weight ratio of the organic solvent in the adhesive composition. The adhesive composition disclosed herein also includes an ethylenically unsaturated compound (B) in addition to the BP polymer (A), and therefore, the ethylenically unsaturated compound (B) can be used as a diluent for the BP polymer (A). Therefore, even in an adhesive composition containing a BP polymer (A) having a certain Mw or more in an amount used or more, an organic solvent for improving the coating properties of the adhesive composition in a normal temperature range (e.g., 20°C to 40°C) is no longer required, or the amount of the organic solvent used can be reduced.

[0162] In some embodiments of the adhesive composition disclosed herein, for the adhesive composition, from the viewpoint of the coating properties in the above-mentioned normal temperature range, the viscosity (BH type viscometer, No. 5 rotor, measured at 10 rpm and a measuring temperature of 30°C. The same below) is appropriately 1000 Pa·s or less, preferably 100 Pa·s or less, and more preferably 50 Pa·s or less. The viscosity of the above-mentioned adhesive composition can be, for example, 30 Pa·s or less, 20 Pa·s or less, 10 Pa·s or less, or 5 Pa·s or less. The lower limit of the viscosity of the adhesive composition is not particularly limited, but from the viewpoint of suppressing the depression of the adhesive composition within the coating range and the overflow of the adhesive composition at the outer edge of the coating range, it is generally appropriate to be 0.1 Pa·s or more, and can be 0.5 Pa·s or more, or 1 Pa·s or more.

[0163] The adhesive composition of some embodiments includes at least a compound having one ethylenically unsaturated group (i.e., a monofunctional monomer) (B1) as the ethylenically unsaturated compound (B). The monofunctional monomer (B1) can be selected from the examples of the ethylenically unsaturated compound (B) described above. The monofunctional monomer (B1) can be used alone or in combination of two or more.

[0164] In the total amount of BP polymer (A) and ethylenically unsaturated compound (B), the weight proportion of monofunctional monomer (B1) can be, for example, 1% by weight or more, 5% by weight or more, or 15% by weight or more. In some embodiments, from the perspective of ease of preparation and coating of the adhesive composition, the weight proportion of the above-mentioned monofunctional monomer (B1) can be 25% by weight or more, 35% by weight or more, or 45% by weight or more. In addition, the weight proportion of the monofunctional monomer (B1) in the above-mentioned total amount can be, for example, 99% by weight or less, usually 95% by weight or less is appropriate, can be 85% by weight or less, can be 75% by weight or less, can be 65% by weight or less, can be 55% by weight or less, or can be 45% by weight or less.

[0165] In the embodiment in which the adhesive composition includes a monofunctional monomer (B1), the glass transition temperature (Tg) obtained by the Fox equation based on the composition of the monofunctional monomer (B1) is not particularly limited, and may be, for example, -80°C or higher and 250°C or lower. The Tg based on the composition of the monofunctional monomer (B1) is generally preferably 150°C or lower, 100°C or lower, 70°C or lower, 50°C or lower, or 30°C or lower, from the viewpoint of compatibility of the polymer derived from the monofunctional monomer (B1) with other components. In some embodiments, from the viewpoint of the surface shape followability of the photo-crosslinkable adhesive, the Tg based on the composition of the monofunctional monomer (B1) is preferably lower than 0°C, more preferably -10°C or lower, -20°C or lower, -30°C or lower, or -40°C or lower. In addition, from the viewpoint of the cohesion of the photo-crosslinkable adhesive and the deformation resistance after photo-crosslinking (for example, the durability of adhesion to the adherend), the Tg based on the composition of the monofunctional monomer (B1) is usually advantageously -60°C or higher, and may be -54°C or higher, -50°C or higher, -45°C or higher, -35°C or higher, or -25°C or higher. The above Tg can be adjusted by the compound used as the monofunctional monomer (B1) and their usage ratio.

[0166] In the adhesive composition comprising the BP polymer (A) and the monofunctional monomer (B1), the photocrosslinkable adhesive formed from the adhesive composition, and the photocrosslinked product thereof, the Tg (hereinafter referred to as "Tg A ”) and the Tg (hereinafter, also referred to as Tg B1 ".) can be obtained by Tg B1 [℃]-Tg A [°C] The calculated Tg difference [°C] (hereinafter also referred to as ΔTg) is set in a range of, for example, above -50°C and below 70°C. It is advantageous from the perspective of compatibility in the photocrosslinkable adhesive and its photocrosslinked product if the absolute value of the above Tg difference is not too large. In some embodiments, ΔTg may be, for example, above -10°C, preferably above 0°C, above 7°C, above 10°C, above 20°C, or above 30°C. In addition, in some embodiments, ΔTg may be, for example, below 50°C, below 30°C, or below 15°C.

[0167] The adhesive composition of some embodiments comprises at least a compound having two or more ethylenically unsaturated groups (i.e., a multifunctional monomer) (B2) as the above-mentioned ethylenically unsaturated compound (B). The multifunctional monomer (B2) can be used alone or in combination of two or more from the examples of the above-mentioned multifunctional monomers. The amount of the multifunctional monomer (B2) can be set in the same manner as the proportion of the multifunctional monomer in the overall monomer components constituting the adhesive composition.

[0168] In the method of using a monofunctional monomer (B1) and a polyfunctional monomer (B2) as an ethylenically unsaturated compound (B), the weight ratio of the monofunctional monomer (B1) in the ethylenically unsaturated compound (B) can be, for example, 1% by weight or more, and it is usually appropriate to be 25% by weight or more, and it can be 50% by weight or more, 75% by weight or more, 95% by weight or more, or 99% by weight or more. In addition, the weight ratio of the monofunctional monomer (B1) in the ethylenically unsaturated compound (B) can be, for example, 99.9% by weight or less, and can be 99.8% by weight or less.

[0169] In the adhesive composition disclosed herein, the ethylenically unsaturated compound (B) may be contained in the form of a partial polymer, or the entire amount thereof may be contained in the form of an unreacted monomer. A preferred embodiment relates to an adhesive composition that contains the ethylenically unsaturated compound (B) in the form of a partial polymer. There is no particular limitation on the polymerization method for partially polymerizing the ethylenically unsaturated compound (B), and various polymerization methods known in the past may be appropriately selected and used, such as: photopolymerization by irradiation with light such as ultraviolet rays; radiation polymerization by irradiation with radiation such as beta rays and gamma rays; thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization; and the like. From the viewpoint of efficiency and simplicity, photopolymerization may be preferably used. According to photopolymerization, the polymerization conversion rate (monomer conversion) can be easily controlled by polymerization conditions such as the amount of light irradiation (amount of light).

[0170] The polymerization conversion rate of the ethylenically unsaturated compound (B) in the above-mentioned partial polymer is not particularly limited. From the viewpoint of the ease of preparation and coating of the adhesive composition, the above-mentioned polymerization conversion rate is usually about 50% by weight or less, preferably about 40% by weight or less (for example, about 35% by weight or less). The lower limit of the polymerization conversion rate is not particularly limited, and is typically about 1% by weight or more, and is usually about 5% by weight or more.

[0171] The adhesive composition containing a partial polymer of an ethylenically unsaturated compound (B) can be obtained, for example, by the following method: using an appropriate polymerization method (e.g., photopolymerization method) to partially polymerize a monomer mixture containing the entire amount of the ethylenically unsaturated compound (B) used to prepare the adhesive composition. In addition, the adhesive composition containing a partial polymer of an ethylenically unsaturated compound (B) can be a mixture of a partial polymer of a monomer mixture containing a portion of the ethylenically unsaturated compound (B) used to prepare the adhesive composition and the remaining ethylenically unsaturated compound (B) or its partial polymer. It should be noted that in this specification, the so-called "complete polymer" refers to a polymerization conversion rate higher than 95% by weight.

[0172] The above-mentioned partial polymer can be prepared, for example, by irradiating ultraviolet light to the ethylenically unsaturated compound. When the above-mentioned partial polymer is prepared in the presence of a BP polymer, the ultraviolet light irradiation conditions can be set in such a way that the ethylenically unsaturated group reacts and the benzophenone structure is not excited by light, thereby obtaining an adhesive composition containing the partial polymer of the ethylenically unsaturated compound and the BP polymer. As the light source, it is preferred to use a light source such as the above-mentioned black light lamp, UV-LED lamp, etc. that can irradiate ultraviolet light that does not contain a component with a wavelength less than 300nm or has a small amount of such a wavelength component.

[0173] Alternatively, the adhesive composition may be prepared by pre-preparing a partial polymer of the ethylenically unsaturated compound (B) and then mixing the partial polymer with the BP polymer. When the partial polymer is prepared by irradiating the ethylenically unsaturated compound with ultraviolet light in the absence of a component containing a benzophenone structure, the ultraviolet light source may be any light source that does not excite the benzophenone structure or a light source that excites the benzophenone structure.

[0174] When preparing a partial polymer of an ethylenically unsaturated compound (B), the reaction of the ethylenically unsaturated group can be promoted by using a photoinitiator. As a photoinitiator, a ketal photoinitiator, an acetophenone photoinitiator, a benzoin ether photoinitiator, an acylphosphine oxide photoinitiator, an α-ketol photoinitiator, an aromatic sulfonyl chloride photoinitiator, a photoactive oxime photoinitiator, a benzoin photoinitiator, a benzyl photoinitiator, a benzophenone photoinitiator, an alkylphenone photoinitiator, a thioxanthone photoinitiator, etc. can be used. It is preferred to use a photoinitiator that absorbs light with a wavelength of more than 300nm (for example, light with a wavelength of more than 300nm and less than 500nm) to generate free radicals. The photoinitiator can be used alone or in combination of two or more.

[0175] (Photoinitiator (C))

[0176] In the adhesive composition, a photoinitiator may be contained as needed for the purpose of improving or imparting photocurability. As the photoinitiator, a ketal photoinitiator, an acetophenone photoinitiator, a benzoin ether photoinitiator, an acylphosphine oxide photoinitiator, an α-ketol photoinitiator, an aromatic sulfonyl chloride photoinitiator, a photoactive oxime photoinitiator, a benzoin photoinitiator, a benzyl photoinitiator, a benzophenone photoinitiator, an alkylphenone photoinitiator, a thioxanthone photoinitiator, etc. may be used. One type of the photoinitiator may be used alone or two or more types may be used in combination as appropriate.

[0177] Specific examples of the ketal-based photoinitiator include 2,2-dimethoxy-1,2-diphenylethane-1-one and the like.

[0178] Specific examples of acetophenone-based photoinitiators include 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, 4-tert-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, methoxyacetophenone, and the like.

[0179] Specific examples of the benzoin ether-based photoinitiator include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, and benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether.

[0180] Specific examples of the acylphosphine oxide-based photoinitiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the like.

[0181] Specific examples of α-ketol photoinitiators include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one, etc. Specific examples of aromatic sulfonyl chloride photoinitiators include 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime photoinitiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin photoinitiators include benzoin, etc. Specific examples of benzyl photoinitiators include benzyl, etc.

[0182] Specific examples of the benzophenone-based photoinitiator include benzoylbenzoic acid, 3,3′-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, and α-hydroxycyclohexylphenylketone.

[0183] Specific examples of the thioxanthone-based photoinitiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0184] As the photoinitiator (C) contained in the adhesive composition, a photoinitiator that generates free radicals by absorbing light with a wavelength of 300 nm or more (e.g., light with a wavelength of 300 nm or more and 500 nm or less) can be preferably used. One photoinitiator can be used alone or two or more photoinitiators can be used in appropriate combination. In some embodiments, a photoinitiator that does not contain a phosphorus element in the molecule can be preferably used. The adhesive composition disclosed herein can be an adhesive composition that does not substantially contain a photoinitiator that contains a phosphorus element in the molecule.

[0185] The content of the photoinitiator in the adhesive composition is not particularly limited and can be set in a manner that the desired effect is suitably exerted. In some embodiments, the content of the photoinitiator can be, for example, about 0.005 parts by weight or more, usually 0.01 parts by weight or more is appropriate, preferably 0.05 parts by weight or more, can be 0.10 parts by weight or more, can be 0.15 parts by weight or more, can be 0.20 parts by weight or more, relative to 100 parts by weight of the monomer component constituting the adhesive composition. By increasing the content of the photoinitiator, the photocurability of the adhesive composition is improved. In addition, the content of the photoinitiator relative to 100 parts by weight of the monomer component constituting the adhesive composition is usually 5 parts by weight or less, preferably 2 parts by weight or less, can be 1 part by weight or less, can be 0.7 parts by weight or less, can be 0.5 parts by weight or less. The situation where the content of the photoinitiator is not too much will become advantageous from the viewpoint of inhibiting the gelation of the adhesive composition.

[0186] (Crosslinking agent)

[0187] In the adhesive composition, known crosslinking agents such as isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, melamine crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, hydrazine crosslinking agents, and amine crosslinking agents can be used as needed. Peroxides can also be used as crosslinking agents. These crosslinking agents can be used alone or in combination of two or more. The photo-crosslinkable adhesive formed by the adhesive composition containing the crosslinking agent preferably contains the crosslinking agent mainly in the form after the crosslinking reaction. By using a crosslinking agent, the cohesive force of the photo-crosslinkable adhesive can be appropriately adjusted.

[0188] The amount used when using a cross-linking agent (the total amount of the cross-linking agents when using more than two cross-linking agents) is not particularly limited. From the perspective of realizing an adhesive that exerts adhesive properties such as bonding force and cohesive force in a well-balanced manner, the amount of the cross-linking agent used is generally about 5 parts by weight or less, which is appropriate relative to 100 parts by weight of the monomer components constituting the adhesive composition, which can be less than 3 parts by weight, which can be less than 1 part by weight, which can be less than 0.50 parts by weight, which can be less than 0.30 parts by weight, which can be less than 0.20 parts by weight. The lower limit of the amount of the cross-linking agent used is not particularly limited, which is an amount greater than 0 parts by weight relative to 100 parts by weight of the monomer components constituting the adhesive composition. In some ways, the amount of the cross-linking agent used can be, for example, more than 0.001 parts by weight, more than 0.01 parts by weight, more than 0.05 parts by weight, or more than 0.10 parts by weight relative to 100 parts by weight of the monomer components constituting the adhesive composition. The technology disclosed herein can also be preferably implemented without using a cross-linking agent.

[0189] (Chain transfer agent)

[0190] The adhesive composition may contain various chain transfer agents known in the past. As the chain transfer agent, thiols such as n-dodecyl mercaptan, tert-dodecyl mercaptan, thioglycolic acid, and α-thioglycerol can be used. Alternatively, a chain transfer agent that does not contain a sulfur atom (non-sulfur chain transfer agent) can also be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenes such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having benzylidene groups such as dibenzylideneacetone, cinnamyl alcohol, and cinnamaldehyde; hydroquinones such as hydroquinone and dihydroxynaphthalene; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; benzyl hydrogens such as diphenylbenzene and triphenylbenzene; and the like. The chain transfer agent can be used alone or in combination of two or more. When a chain transfer agent is used, the amount used may be, for example, about 0.01 to 1 part by weight based on 100 parts by weight of the monomer component. The technology disclosed herein may also be preferably implemented without using a chain transfer agent.

[0191] As other components that can be included in the adhesive composition, silane coupling agents can be cited. By using silane coupling agents, the peel strength for adherends (e.g., glass plates) can be improved. In addition, in the photo-crosslinkable adhesive disclosed herein, a silane coupling agent can be contained. The photo-crosslinkable adhesive containing a silane coupling agent can be suitably formed using an adhesive composition containing a silane coupling agent. The silane coupling agent can be used alone or in combination of two or more.

[0192] The adhesive composition disclosed herein may contain various common additives in the adhesive field such as tackifier resins (e.g., rosin-based, petroleum-based, terpene-based, phenol-based, ketone-based, etc.), viscosity modifiers (e.g., thickeners), leveling agents, antioxidants, plasticizers, fillers, colorants such as pigments and dyes, stabilizers, preservatives, anti-aging agents, etc. as other optional components as needed. With regard to such various additives, conventionally known additives may be used by conventional methods, and detailed descriptions thereof are omitted because they do not particularly characterize the present invention.

[0193] It should be noted that the technology disclosed herein can exert good bonding strength without using the above-mentioned tackifying resin. Therefore, in some ways, the content of the above-mentioned tackifying resin in the above-mentioned adhesive layer or adhesive composition can be less than 10 parts by weight, and then less than 5 parts by weight relative to 100 parts by weight of the monomer component. The content of the above-mentioned tackifying resin can be less than 1 part by weight (for example, less than 0.5 parts by weight), and can be less than 0.1 parts by weight (0 parts by weight or more and less than 0.1 parts by weight). The above-mentioned adhesive layer or adhesive composition may not contain tackifying resin.

[0194] (Formation of Photo-crosslinkable Adhesive)

[0195] The adhesive composition disclosed herein is constituted in a manner that a photo-crosslinkable adhesive containing a BP polymer can be formed by curing the adhesive composition. The curing of the adhesive composition is preferably carried out in a manner that the ethylenically unsaturated groups contained in the adhesive composition react and the benzophenone structure contained in the adhesive composition remains. The above-mentioned curing can preferably be carried out by irradiation with active energy rays. As the active energy ray used to form the photo-crosslinkable adhesive, ultraviolet rays are preferably not included in the components with a wavelength of less than 300nm or ultraviolet rays with less wavelength components are more preferably not included in the components with a wavelength of less than 300nm.

[0196] The photocrosslinkable adhesive disclosed herein can be manufactured using any adhesive composition disclosed herein. The photocrosslinkable adhesive may include a BP polymer (A) and a polymer (E) derived from an ethylenically unsaturated compound (B). In some preferred embodiments, the adhesive composition may be a composition in which the ethylenically unsaturated compound (B) does not contain an ethylenically unsaturated BP. According to the adhesive composition of such a composition, a photocrosslinkable adhesive comprising a BP polymer (A) and a polymer (E) derived from an ethylenically unsaturated compound (B), and the polymer (E) is a non-BP polymer, can be manufactured.

[0197] According to this specification, a method for manufacturing a photo-crosslinkable adhesive that can be photo-crosslinked using a benzophenone structure can be provided. Its manufacturing method includes the following steps: preparing an adhesive composition comprising an ethylenically unsaturated group and a benzophenone structure; and irradiating the above-mentioned adhesive composition with active energy rays (preferably ultraviolet rays). The above-mentioned adhesive composition may contain a photoinitiator. The irradiation of active energy rays for curing the adhesive composition is preferably carried out in a manner that allows the ethylenically unsaturated group to react and leaves the benzophenone structure residual. As the above-mentioned adhesive composition, an adhesive composition comprising a BP polymer (A) and an ethylenically unsaturated compound (B) can be preferably used. The above-mentioned photo-crosslinkable adhesive manufacturing method can be preferably implemented using any adhesive composition disclosed herein. As a light source for curing the adhesive composition to form a photo-crosslinkable adhesive, it is preferred to use the above-mentioned black light lamp, UV-LED lamp, etc., which can irradiate ultraviolet rays that do not contain components with a wavelength less than 300nm or have less components of this wavelength.

[0198] <Adhesive Sheet>

[0199] According to the present description, a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed of any of the photo-crosslinkable pressure-sensitive adhesives disclosed herein can be provided.

[0200] One example of the structure of the adhesive sheet disclosed herein is shown in Figure 1 The adhesive sheet 1 is a single-sided adhesive sheet including an adhesive layer 10 having one surface 10A serving as an attachment surface (adhesive surface) for an adherend, and a substrate 20 laminated on the other surface 10B of the adhesive layer 10. The adhesive layer 10 is bonded to one surface 20A of the substrate 20. As the substrate 20, a plastic film such as a polyester film can be used. The substrate 20 can be an optical film such as a polarizing plate. Figure 1 In the example shown, the adhesive layer 10 has a single-layer structure. The adhesive sheet 1 before use (before being attached to an adherend) may be, for example, Figure 1 As shown in the figure, the adhesive surface 10A is protected by the release liner 30 whose at least the adhesive layer side becomes the releasable surface (release surface), and the adhesive sheet 50 with a release liner is in the form. Alternatively, it can also be in the form of: the second surface 20B (the surface on the opposite side of the first surface 20A, also referred to as the back side) of the substrate 20 becomes the release surface, and the adhesive surface 10A is abutted against the second surface 20B of the substrate 20, thereby protecting the adhesive surface 10A.

[0201] The release liner is not particularly limited, and for example, a release liner having a release treatment on the surface of a liner substrate such as a resin film or paper, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. In the above release treatment, for example, a release treatment agent such as a silicone-based or long-chain alkyl-based release agent can be used. In some embodiments, a release-treated resin film can be preferably used as the release liner.

[0202] The adhesive sheet disclosed herein may also be in the form of a double-sided adhesive sheet without a substrate formed by an adhesive layer. Figure 2 As shown, before use, each surface 10A, 10B of the adhesive layer 10 may be protected by a release liner 31, 32 whose at least the adhesive layer side becomes a releasable surface (release surface). Alternatively, the following form may be adopted: the back side (the surface on the opposite side to the adhesive side) of the release liner 31 becomes the release surface, and the adhesive surface 10B is abutted against the back side of the release liner 31, thereby protecting the adhesive surfaces 10A, 10B. Such a double-sided adhesive sheet without a substrate can be used, for example, in a manner in which a substrate is bonded to any one surface of the adhesive layer.

[0203] The adhesive sheet disclosed herein may be a constituent element of an optical member with an adhesive sheet obtained by bonding an optical member to one surface of an adhesive layer. For example, Figure 1 The adhesive sheet 1 shown can be Figure 3 The components of the optical member 100 with a pressure-sensitive adhesive sheet are shown in FIG. 1 , wherein the optical member 70 is bonded to one surface 10A of the pressure-sensitive adhesive layer 10. The optical member may be, for example, a glass plate, a resin film, or a metal plate.

[0204] The adhesive layer constituting the adhesive sheet disclosed herein can be a cured layer of the corresponding adhesive composition. For example, the adhesive layer can be an adhesive layer formed by imparting (e.g., applying) the above-mentioned adhesive composition to an appropriate surface and then curing the adhesive composition. The curing of the adhesive composition can preferably be carried out by irradiation with active energy rays. As the active energy ray for forming the adhesive layer, it is preferably ultraviolet rays, more preferably ultraviolet rays without a component having a wavelength of less than 300nm or the wavelength component.

[0205] The coating of the adhesive composition can be carried out using a commonly used coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a rod coater, a knife coater, a spray coater, etc. For an adhesive sheet having a substrate, as a method of providing an adhesive layer on the substrate, a direct method of directly applying the adhesive composition to the substrate to form the adhesive layer can be used, and a transfer method of transferring the adhesive layer formed on the release surface to the substrate can also be used.

[0206] The thickness of the adhesive layer is not particularly limited, for example, it can be about 3μm to 2000μm. From the perspective of surface shape tracking (for example, step tracking) and the adhesion of the adherend, in some ways, the thickness of the adhesive layer can be, for example, 5μm or more, 10μm or more is appropriate, preferably 20μm or more, and more preferably 30μm or more. The thickness of the adhesive layer can be 50μm or more, can be greater than 50μm, can be 70μm or more, can be 100μm or more, can be 120μm or more. In addition, from the perspective of preventing the occurrence of slurry residue caused by the cohesive failure of the adhesive layer, in some ways, the thickness of the adhesive layer can be, for example, 1000μm or less, can be 700μm or less, can be 500μm or less, can be 300μm or less, and can be 200μm or less or 170μm or less. The technology disclosed herein can also be appropriately implemented in the form of an adhesive sheet with a thickness of 130μm or less, 90μm or less, 60μm or less, or 40μm or less. It should be noted that in an adhesive sheet including an adhesive layer having a multilayer structure of two or more layers, the thickness of the adhesive layer refers to the thickness from the adhesive surface attached to the adherend to the surface on the opposite side of the adhesive surface. From the viewpoint of surface followability, the adhesive layer of the multilayer structure preferably does not contain a layer other than the adhesive layer (e.g., a resin film) within the thickness of the adhesive layer (i.e., between the adhesive surface attached to the adherend and the surface on the opposite side of the adhesive surface).

[0207] <Base material>

[0208] The adhesive sheet involved in some methods can be a form of an adhesive sheet with a substrate including a substrate bonded to an adhesive layer. The material of the substrate is not particularly limited and can be appropriately selected according to the purpose of use, the method of use, etc. of the adhesive sheet. As non-limiting examples of usable substrates, there can be cited plastic films (resin films) such as polyolefin films with polyolefins such as polypropylene and ethylene-propylene copolymer as the main component, polyester films with polyesters such as polyethylene terephthalate and polybutylene terephthalate as the main component, and polyvinyl chloride films with polyvinyl chloride as the main component; foam sheets formed by foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; fabrics and non-woven fabrics formed by various fibrous substances (which can be natural fibers such as hemp and cotton, synthetic fibers such as polyester and vinylon, and semi-synthetic fibers such as acetate, etc.) alone or in a blend; paper such as Japanese paper, high-quality paper, kraft paper, and crepe paper; metal foils such as aluminum foil and copper foil; and so on. It can be a substrate composed of them. Examples of such a composite structure substrate include a substrate having a structure in which a metal foil and the above-mentioned plastic film are laminated, and a plastic sheet reinforced with inorganic fibers such as glass cloth.

[0209] As the substrate of the adhesive sheet disclosed herein, various films (hereinafter, also referred to as support films) can be preferably used. The above-mentioned support film can be a porous film such as a foam film, a non-woven fabric sheet, etc., or a non-porous film, or a film having a structure in which a porous layer and a non-porous layer are stacked. In some embodiments, as the above-mentioned support film, a film containing a (self-supporting or non-dependent) resin film that can independently maintain a shape as a base film can be preferably used. The so-called "resin film" here is a non-porous structure, typically referring to a resin film that is substantially free of bubbles (non-porous). Therefore, the above-mentioned resin film is a concept distinguished from a foam film and a non-woven fabric. The above-mentioned resin film can be a single-layer structure, or a multilayer structure (such as a three-layer structure) of more than two layers.

[0210] As the resin material constituting the resin film, for example, polyester, polyolefin, polycycloolefin derived from a monomer having an aliphatic ring structure such as a norbornene structure, polyamide (PA) such as nylon 6, nylon 66, partially aromatic polyamide, polyimide (PI) such as transparent polyimide (CPI), polyamideimide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), polystyrene, ABS resin, polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene (PTFE) and other fluororesins, acrylic resins such as polymethyl methacrylate, cellulose diacetate, cellulose triacetate (TAC) and other cellulose polymers, vinyl butyral polymers, arylate polymers, polyoxymethylene polymers, epoxy polymers and the like resins can be used. The above-mentioned resin film can be a resin film formed using a resin material containing only one such resin, or a resin film formed using a resin material obtained by blending two or more of them. The resin film may be unstretched or stretched (for example, uniaxially stretched or biaxially stretched).

[0211] Preferred examples of the resin material constituting the resin film include polyester resins, PPS resins, polyolefin resins, and polyimide resins. Here, polyester resins refer to resins containing polyester at a ratio higher than 50% by weight. Similarly, PPS resins refer to resins containing PPS at a ratio higher than 50% by weight, polyolefin resins refer to resins containing polyolefins at a ratio higher than 50% by weight, and polyimide resins refer to resins containing polyimides at a ratio higher than 50% by weight.

[0212] As the polyester resin, typically, a polyester resin containing a polyester obtained by polycondensing a dicarboxylic acid and a diol as a main component can be used. Specific examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate, etc.

[0213] As the polyolefin resin, one polyolefin can be used alone, or two or more polyolefins can be used in combination. The polyolefin can be, for example, a homopolymer of an α-olefin, a copolymer of two or more α-olefins, a copolymer of one or more α-olefins and other vinyl monomers, etc. As specific examples, ethylene-propylene copolymers such as polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, ethylene-ethyl acrylate copolymers, etc. can be cited. Low-density (LD) polyolefins and high-density (HD) polyolefins can both be used. Examples of polyolefin resin films include unstretched polypropylene (CPP) films, biaxially stretched polypropylene (OPP) films, low-density polyethylene (LDPE) films, linear low-density polyethylene (LLDPE) films, medium-density polyethylene (MDPE) films, high-density polyethylene (HDPE) films, polyethylene (PE) films obtained by blending two or more polyethylene (PE), and PP / PE blended films obtained by blending polypropylene (PP) and polyethylene (PE).

[0214] As a specific example of a resin film that can be preferably used as a substrate, PET film, PEN film, PPS film, PEEK film, CPI film, CPP film and OPP film can be mentioned. From the perspective of strength, as a preferred example, PET film, PEN film, PPS film, PEEK film, CPI film can be mentioned. From the perspective of ease of acquisition, dimensional stability, optical properties, etc., as a preferred example, PET film, CPI film, TAC film can be mentioned.

[0215] In the resin film, known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, anti-blocking agents, etc. can be added as needed. The amount of the additives is not particularly limited and can be appropriately set according to the use of the adhesive sheet, etc.

[0216] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.

[0217] The substrate may be substantially composed of such a resin film. Alternatively, the substrate may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printed layer for giving a desired appearance to the substrate or adhesive sheet, a laminated layer, an antistatic layer, a primer layer, a peeling layer and other surface treatment layers. In addition, the substrate may be an optical component (e.g., an optical film) described later.

[0218] The thickness of the substrate is not particularly limited and can be selected according to the purpose of use and the method of use of the adhesive sheet. The thickness of the substrate can be, for example, less than 1000 μm, less than 500 μm, less than 100 μm, less than 70 μm, less than 50 μm, less than 25 μm, less than 10 μm, or less than 5 μm. If the thickness of the substrate becomes smaller, the softness of the adhesive sheet and the tendency to follow the surface shape of the adherend are improved. In addition, from the viewpoint of operability, processability, etc., the thickness of the substrate can be, for example, more than 2 μm, greater than 5 μm or greater than 10 μm. In some ways, the thickness of the substrate can be, for example, more than 20 μm, more than 35 μm, or more than 55 μm.

[0219] For the surface of one side bonded to the adhesive layer in the substrate, corona discharge treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, coating of primer (primer), antistatic treatment and other previously known surface treatments can be implemented as needed. Such surface treatment can be a treatment for improving the adhesion between the substrate and the adhesive layer, in other words, the anchoring of the adhesive layer to the substrate. The composition of the primer is not particularly limited and can be appropriately selected from known primer compositions. The thickness of the primer layer is not particularly limited, and is usually about 0.01 μm to 1 μm, preferably about 0.1 μm to 1 μm.

[0220] For the surface of the substrate that is opposite to the side joined to the adhesive layer (hereinafter, also referred to as the back side), a peeling treatment, a treatment to improve adhesion or cohesion, an antistatic treatment, or other surface treatments known in the past may be applied as needed. For example, by surface treating the back side of the substrate with a peeling agent, the unwinding force of the adhesive sheet wound into a roll can be reduced. As the peeling agent, a silicone peeling agent, a long-chain alkyl peeling agent, an olefin peeling agent, a fluorine peeling agent, a fatty acid amide peeling agent, molybdenum sulfide, silica powder, etc. can be used.

[0221] <Characteristics of adhesive sheets>

[0222] (Peel Strength)

[0223] In the adhesive sheet disclosed herein, the peel strength measured by the above-mentioned peel strength determination step, more specifically the peel strength measured by the method described in the embodiment described later, for example, can be about 0.5N / 10mm or more, and it is usually appropriate to be about 1.0N / 10mm or more. From the viewpoint of improving the bonding reliability, the above-mentioned peel strength is preferably about 1.5N / 10mm or more, and more preferably about 2.0N / 10mm or more. In the adhesive sheet involved in one embodiment, the above-mentioned peel strength can be, for example, about 3.0N / 10mm or more, about 4.5N / 10mm or more, or about 5.5N / 10mm or more. The adhesive sheet disclosed herein can also be implemented in a manner where the peel strength is about 5.7N / 10mm or more, about 6.5N / 10mm or more, about 7N / 10mm or more, about 8N / 10mm or more, about 9N / 10mm or more, about 10N / 10mm or more, about 11N / 10mm or more, about 12N / 10mm or more, or about 13N / 10mm or more. Such strong adhesive force can be ideally achieved by using a silane coupling agent, for example. The upper limit of the peel strength is not particularly limited, and can be, for example, 25 N / 10 mm or less, and can be 20 N / 10 mm or less, 15 N / 10 mm or less, 10 N / 10 mm or less, or 8 N / 10 mm or less in consideration of the balance with other physical properties.

[0224] (Haze value)

[0225] In the technology disclosed herein, it is appropriate for the haze value of the adhesive sheet to be about 10% or less, and can be about 5% or less (for example, about 3% or less). In some embodiments, the haze value of the adhesive sheet is preferably 1.0% or less. Such a highly transparent adhesive sheet is suitable for optical applications requiring high light transmittance. The haze value of the adhesive sheet can be lower than 1.0%, lower than 0.7%, and can be lower than 0.5% (for example, 0 to 0.5%). The haze value can also preferably be applied to the haze value of the adhesive layer formed by a photo-crosslinkable adhesive.

[0226] Here, the so-called "haze value" refers to the ratio of diffused transmitted light to the total transmitted light when the object to be measured is irradiated with visible light. It is also called haze value. The haze value can be expressed by the following formula.

[0227] Th[%]=Td / Tt×100

[0228] In the above formula, Th is the haze value [%], Td is the scattered light transmittance, and Tt is the total light transmittance.

[0229] The haze value can be measured using a haze meter (for example, "MR-100" manufactured by Murakami Color Research Laboratory). The haze value can be adjusted by, for example, selecting the composition and thickness of the pressure-sensitive adhesive layer.

[0230] <Laminate Manufacturing Method>

[0231] The photocrosslinkable adhesive disclosed herein can be preferably used in a manner that the photocrosslinkable adhesive is laminated on a member as an adherend and the photocrosslinkable adhesive is photocrosslinked. Thus, a laminate in which the photocrosslinked material and the adherend are bonded with good reliability can be manufactured. The photocrosslinking of the photocrosslinkable adhesive can be performed by irradiating the photocrosslinkable adhesive with active energy rays. As active energy rays, it is preferred that ultraviolet rays containing wavelength components that can excite the benzophenone structure contained in the photocrosslinkable adhesive (for example, ultraviolet rays containing components with a wavelength lower than 300nm) are included. The photocrosslinkable adhesive can be used for the manufacture of the laminate in the form of an adhesive sheet having an adhesive layer formed by the photocrosslinkable adhesive. Therefore, according to the present specification, a method for manufacturing a laminate comprising the following steps in sequence can be provided: an adhesive sheet having an adhesive layer formed by any photocrosslinkable adhesive disclosed herein is attached to an adherend; and the adhesive sheet is irradiated with active energy rays to photocrosslink the photocrosslinkable adhesive.

[0232] When the PSA sheet used in a manner of being bonded to an adherend and then photo-crosslinked has a PSA layer having a multilayer structure, the PSA layer to be photo-crosslinked may be a part of the layers (eg, one layer) or all the layers included in the multilayer structure.

[0233] The photocrosslinkable adhesive disclosed herein can be used in the following manner: for example, in the form of an adhesive sheet having an adhesive layer formed by the photocrosslinkable adhesive, which is stacked on a surface having a step difference. The above-mentioned photocrosslinkable adhesive can exhibit good surface shape tracking (step difference tracking) on ​​the surface of the adherend having the step difference. After stacking the photocrosslinkable adhesive, a highly reliable joint can be formed by photocrosslinking the photocrosslinkable adhesive. The above-mentioned step difference can be, for example, a printed layer provided on the surface of the above-mentioned adherend. The height of the above-mentioned step difference can be, for example, more than 5 μm, more than 10 μm, more than 20 μm, or more than 30 μm. The height of the above-mentioned step difference can be, for example, less than 100 μm, preferably less than 70 μm.

[0234] <Application>

[0235] The use of the photo-crosslinkable adhesive disclosed herein is not particularly limited, and can be used for various purposes. For example, the photo-crosslinkable adhesive disclosed herein can be used for fixing, joining, molding, decoration, protection, support, etc. of components constituting various products in the form of an adhesive sheet having an adhesive layer formed by the photo-crosslinkable adhesive. The material constituting at least the surface of the above-mentioned component can be, for example, glass such as alkali glass and alkali-free glass; metal materials such as stainless steel (SUS) and aluminum; ceramic materials such as alumina and silica; resin materials such as acrylic resin, ABS resin, polycarbonate resin, polystyrene resin, transparent polyimide resin; and so on. The above-mentioned component can be, for example, a component constituting various portable devices (portable devices), automobiles, home appliances, etc. In addition, for the above-mentioned component, the surface to which the adhesive sheet is attached can be a coating surface formed by a coating of an acrylic system, a polyester system, an alkyd resin system, a melamine system, a urethane system, an acid-epoxy crosslinking system, or a composite system thereof (such as an acrylic melamine system, an alkyd resin melamine system), or a plated surface of a galvanized steel sheet. In addition, the member may be any supporting film (eg, resin film) exemplified as a material that can be used for the substrate. The adhesive sheet disclosed herein may be a component of a member with an adhesive sheet obtained by bonding such a member to at least one surface of an adhesive layer.

[0236] As an example of preferred use, optical use can be cited. More specifically, for example, as an optical adhesive sheet used for the use of bonding optical components (optical component bonding), the manufacture of products (optical products) using the above optical components, etc., the adhesive sheet disclosed herein can be preferably used.

[0237] The above-mentioned optical component refers to a component having optical properties (for example, polarization, light refraction, light scattering, light reflectivity, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As the above-mentioned optical component, as long as it is a component with optical properties, it is not particularly limited. For example, components constituting devices (optical devices) such as display devices (image display devices) and input devices or components used by these devices can be cited. For example, polarizing plates, wavelength plates, phase difference plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coating (HC) films, impact absorption films, anti-fouling films, photochromic films, dimming films, transparent conductive films (ITO films), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates, and components stacked with them (sometimes collectively referred to as "functional films"). ) etc. It should be noted that the above-mentioned “plate” and “film” each include plate-shaped, film-shaped, sheet-shaped and the like. For example, “polarizing film” includes “polarizing plate”, “polarizer” and the like.

[0238] Examples of the display device include liquid crystal display devices, organic EL (electroluminescent) display devices, PDP (plasma display panel), electronic paper, etc., and are particularly preferably applied to foldable display devices and vehicle-mounted display devices that include expensive components. In addition, examples of the input device include touch panels, etc.

[0239] The optical component is not particularly limited, and examples thereof include components formed of glass, acrylic resin, polycarbonate, polyethylene terephthalate, metal thin film, etc. (e.g., sheet-shaped, film-shaped, plate-shaped components). It should be noted that the "optical component" in this specification also includes components (design films, decorative films, surface protection films, etc.) that play a decorative and protective role while maintaining the visual recognizability of display devices and input devices.

[0240] There is no particular limitation on the method of bonding optical components using the adhesive sheet disclosed herein, and for example, it may be (1) a method of bonding optical components to each other via the adhesive sheet disclosed herein, (2) a method of bonding optical components to components other than optical components via the adhesive sheet disclosed herein, or (3) a method in which the adhesive sheet disclosed herein contains an optical component and the adhesive sheet is bonded to an optical component or a component other than an optical component. It should be noted that in the above-mentioned method (3), the adhesive sheet containing an optical component may be, for example, an adhesive sheet whose substrate is an optical component (for example, an optical film). Such an adhesive sheet containing an optical component as a substrate may also be considered as an adhesive optical component (for example, an adhesive optical film). In addition, in the case where the adhesive sheet disclosed herein is an adhesive sheet of a type having a substrate and the above-mentioned functional film is used as the above-mentioned substrate, the adhesive sheet disclosed herein may also be considered as an "adhesive functional film" having an adhesive layer disclosed herein on at least one side of the functional film.

[0241] The peeling method disclosed herein can be preferably applied to the peeling of an adhesive sheet attached to a non-water-absorbing smooth surface such as a glass plate, a metal plate, a resin plate, etc. In addition, the peeling method disclosed herein can be preferably used as a method for peeling an adhesive sheet from any of the above-mentioned optical components. Among them, it is suitable as a method for peeling an adhesive sheet attached to a glass plate such as an alkali glass or an alkali-free glass.

[0242] It should be noted that the matters disclosed in this specification include the following matters.

[0243] (1) A photo-crosslinkable adhesive comprising a polymer having a benzophenone structure in a side chain,

[0244] The photo-crosslinkable adhesive is a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a benzophenone-containing component, and

[0245] The emission of volatile organic compounds is less than 500 μg / g.

[0246] (2) The photo-crosslinkable adhesive according to (1) above, wherein the benzophenone structure-containing component is a polymer having a benzophenone structure in a side chain.

[0247] (3) The photo-crosslinkable adhesive according to (1) or (2), wherein the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive at 80°C is equal to the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive when the photo-crosslinkable adhesive is subjected to a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The relationship between the shear storage elastic modulus Gc' [kPa] at 80°C of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays satisfies the following formula:

[0248] Gc'[kPa]-Gb'[kPa]≥2kPa.

[0249] (4) The photo-crosslinkable adhesive according to any one of (1) to (3) above, wherein the photo-crosslinkable adhesive is prepared by using a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The shear storage modulus Gc' [kPa] at 80° C. of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays is 40 kPa or more.

[0250] (5) A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed of the photo-crosslinkable pressure-sensitive adhesive described in any one of (1) to (4) above and (13) to (18) below.

[0251] (6) The pressure-sensitive adhesive sheet according to (5) above, wherein the peel strength measured by the following procedure is 1.0 N / 10 mm or more.

[0252] [Peel strength measurement procedure]

[0253] The surface of the adhesive layer was pressed against the glass plate by reciprocating a 2 kg rubber roller, and then autoclaved (50° C., 0.5 MPa, 15 minutes). Then, a high pressure mercury lamp was used to heat the glass plate at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The glass plate was irradiated with ultraviolet rays from the glass plate side under the conditions of , and then the adhesive sheet was peeled off from the glass plate at a tension speed of 300 mm / min and a peeling angle of 180 degrees in an atmosphere of 25° C., and the peel strength at this time was measured.

[0254] (7) A method for manufacturing a laminate, comprising:

[0255] laminating the photo-crosslinkable adhesive described in any one of (1) to (4) above and (13) to (18) below and a member; and

[0256] The photo-crosslinkable adhesive is photo-crosslinked by reacting the benzophenone structure contained in the photo-crosslinkable adhesive.

[0257] (8) A method for producing a photocrosslinkable adhesive, comprising:

[0258] preparing an adhesive composition comprising a polymer (A) having a benzophenone structure in a side chain and an ethylenically unsaturated compound (B); and

[0259] irradiating the adhesive composition with active energy rays;

[0260] Here, the irradiation with the active energy rays is performed so that the ethylenically unsaturated group of the ethylenically unsaturated compound (B) reacts and the benzophenone structure of the polymer (A) remains.

[0261] (9) The method according to the above (8), wherein the adhesive composition contains a compound (B1) having one ethylenically unsaturated group as the ethylenically unsaturated compound (B).

[0262] (10) The method according to (8) or (9) above, wherein the adhesive composition contains a compound (B2) having two or more ethylenically unsaturated groups as the ethylenically unsaturated compound (B).

[0263] (11) The method according to any one of (8) to (10) above, wherein the adhesive composition further comprises a photoinitiator (C).

[0264] (12) An adhesive composition for use in the production of a photo-crosslinkable adhesive comprising a polymer having a benzophenone structure in a side chain (for example, the photo-crosslinkable adhesive described in any one of (1) to (4) above and (13) to (18) below),

[0265] The adhesive composition comprises:

[0266] A polymer (A) having a benzophenone structure in a side chain;

[0267] an ethylenically unsaturated compound (B); and

[0268] A photoinitiator (C) that absorbs light with a wavelength of 300nm to 500nm and generates free radicals,

[0269] The weight fraction of the compound (B2) having two or more ethylenically unsaturated groups in the entire monomer components constituting the adhesive composition is less than 5 weight %.

[0270] (13) A photo-crosslinkable adhesive comprising a polymer having a benzophenone structure in a side chain.

[0271] (14) The photo-crosslinkable adhesive according to (13) above, comprising two or more polymers having different monomer compositions, wherein at least one of the two or more polymers is a polymer having a benzophenone structure in a side chain.

[0272] (15) The photo-crosslinkable adhesive according to (12) or (13) above, wherein the emission amount of volatile organic compounds is 500 μg / g or less.

[0273] (16) The photo-crosslinkable adhesive according to any one of (13) to (15) above, which is a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a component containing a benzophenone structure.

[0274] (17) The photo-crosslinkable adhesive according to any one of (13) to (16), wherein the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive at 80°C is equal to the shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive when the photo-crosslinkable adhesive is subjected to a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The relationship between the shear storage elastic modulus Gc' [kPa] at 80°C of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays satisfies the following formula:

[0275] Gc'[kPa]-Gb'[kPa]≥2kPa.

[0276] (18) The photo-crosslinkable adhesive according to any one of (13) to (17) above, wherein the photo-crosslinkable adhesive is subjected to a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The shear storage modulus Gc' [kPa] at 80° C. of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays is 40 kPa or more.

[0277] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are based on weight.

[0278] <Example 1>

[0279] (Preparation of Adhesive Composition)

[0280] An acrylic copolymer having a benzophenone structure in the side chain (manufactured by BASF, trade name: acResinUV3532, Tg: -60°C, Mw: 25×10 4 , BP equivalent: 10 mg / g), 60 parts of 2-ethylhexyl acrylate (2EHA), 30 parts of N-vinyl-2-pyrrolidone (NVP), 0.2 parts of 1,6-hexanediol diacrylate (HDDA), and 0.15 parts of a photoinitiator P1 (manufactured by IGM Regins, trade name: Omnirad 651) having an absorption peak in the wavelength range of 300 nm to 500 nm were mixed to prepare an adhesive composition C1 for preparing a photocrosslinkable adhesive. The viscosity of the adhesive composition C1 (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature of 30° C.) was 2.4 Pa·s, and the organic solvent content was less than 1% by weight.

[0281] (Preparation of Photo-crosslinkable Adhesive)

[0282] The adhesive composition C1 prepared above was applied to the release surface of a release film R1 (MRF#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm, which was used as the release surface on one side of the polyester film, and then covered with a release film R2 (MRE#38, manufactured by Mitsubishi Resins Co., Ltd.) with a thickness of 38 μm, which was used as the release surface on one side of the polyester film, to block the air. A black light (manufactured by Toshiba Corporation, trade name FL15BL) was used from one side of the laminate to illuminate the laminate at an illumination of 5 mW / cm 2 、Accumulated light intensity 800mJ / cm 2 Thus, a photo-crosslinkable adhesive A1 as a cured product of the adhesive composition C1 was obtained in the form of an adhesive layer (substrate-free adhesive sheet) having a thickness of 150 μm sandwiched between the release films R1 and R2.

[0283] The illuminance of the black light lamp is a value measured by an industrial UV detector (manufactured by TOPCON, trade name: UVR-T1, light receiving unit model: UD-T36) with a peak sensitivity wavelength of about 350 nm.

[0284] (Production of Laminated Body)

[0285] The release film R2 was peeled off from the photo-crosslinkable adhesive A1 obtained above, and the film was bonded to a corona-treated polyethylene terephthalate (PET) film having a thickness of 75 μm, thereby obtaining a single-sided adhesive sheet S1 with a substrate, in which one side of the adhesive layer formed of the photo-crosslinkable adhesive A1 was fixed to the PET film (substrate).

[0286] The release film R1 was removed from the adhesive surface of the single-sided adhesive sheet, and the exposed adhesive surface was pressed against a glass plate (Gorilla Glass 3, manufactured by Corning) as a component by rolling a 2 kg rubber roller back and forth once. The sheet was autoclaved (50°C, 0.5 MPa, 15 minutes) and then heated with a high-pressure mercury lamp (manufactured by Toshiba, trade name H3000L / 22N) at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The adhesive A1 was photo-crosslinked by irradiating ultraviolet rays from the glass plate side under the conditions of . As described above, a laminate having a structure of PET film / adhesive layer / glass plate was prepared.

[0287] The illuminance value of the high-pressure mercury lamp is a measured value obtained by using an industrial UV detector (manufactured by TOPCON, trade name: UVR-T1, light receiving unit model: UD-T25) with a peak sensitivity wavelength of about 350 nm.

[0288] <Example 2>

[0289] An adhesive composition C2 for preparing a photo-crosslinkable adhesive was prepared by mixing 30 parts of an acrylic copolymer having a benzophenone structure in a side chain (manufactured by BASF, trade name: acResin UV3532), 38 parts of 2EHA, 4 parts of NVP, 28 parts of isobornyl acrylate (IBXA), 0.04 parts of HDDA, 0.08 parts of 3-acryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicone Co., Ltd., trade name: KBM-5103), and 0.2 parts of a photoinitiator P2 having an absorption peak in the wavelength range of 300 nm to 500 nm (manufactured by IGM Regins, trade name: Omnirad184). The viscosity of the adhesive composition C2 (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature 30° C.) was 0.4 Pa·s, and the organic solvent content was less than 1% by weight.

[0290] Photo-crosslinkable adhesive A2 was obtained as a cured product of adhesive composition C2 in the form of an adhesive layer (substrate-less adhesive sheet) having a thickness of 150 μm sandwiched between release films R1 and R2 in the same manner as in Example 1 except that adhesive composition C2 was used instead of adhesive composition C1.

[0291] A laminate having a structure of PET film / adhesive layer / glass plate was prepared in the same manner as in Example 1 using the photo-crosslinkable adhesive A2.

[0292] <Example 3>

[0293] A monomer mixture consisting of 78 parts of 2EHA, 18 parts of NVP and 4 parts of 2-hydroxyethyl acrylate (HEA) and 0.07 parts of a mixture of photoinitiators P1 and P2 in a weight ratio of 1:1 were placed in a four-necked flask, and photopolymerized by irradiation with ultraviolet light using the above-mentioned high-pressure mercury lamp under a nitrogen atmosphere until the viscosity (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 15 Pa·s, thereby preparing a monomer slurry containing a partial polymer of the above-mentioned monomer mixture. To the monomer slurry, 10 parts of NVP, 20 parts of IBXA, 0.15 parts of HDDA, 0.2 parts of α-methylstyrene dimer (manufactured by NOF Corporation, trade name: NOFMER MSD) as a chain transfer agent, and 0.5 parts of photoinitiator P1 (Omnirad 651) were added and mixed to prepare an adhesive composition C3.

[0294] The adhesive composition C3 prepared above was applied to the release surface of a release film R1 (MRF#38 manufactured by Mitsubishi Plastics Co., Ltd.), and the release film R2 (MRE#38 manufactured by Mitsubishi Plastics Co., Ltd.) was covered to block air. The laminate was irradiated from one side with an illumination of 5 mW / cm 2 At this time, the ultraviolet irradiation time is adjusted so that about 5% of the total ethylenically unsaturated compound used in the preparation of the adhesive composition C3 remains in an unreacted state (that is, so that the polymerization conversion rate becomes about 95%). As described above, the adhesive A3 as a cured product of the above-mentioned adhesive composition C3 is obtained in the form of an adhesive layer (adhesive sheet without a substrate) with a thickness of 150 μm sandwiched between the above-mentioned release films R1 and R2.

[0295] Using this adhesive A3, a laminate having a structure of PET film / adhesive layer / glass plate was prepared in the same manner as in Example 1.

[0296] <Example 4>

[0297] An acrylic copolymer having a benzophenone structure in the side chain (manufactured by BASF, trade name: acResin A260UV, Tg: -39°C, Mw: 19×10 4 , BP equivalent: 2 mg / g) 50 parts, n-butyl acrylate (BA) 34 parts, NVP 16 parts, and photoinitiator P2 (Omnirad 184) 0.2 parts were mixed to prepare an adhesive composition C4 for making a photocrosslinkable adhesive. The viscosity of the adhesive composition C4 (BH type viscometer, No. 5 rotor, 10 rpm, measurement temperature 30° C.) was 27 Pa·s, and the organic solvent content was less than 1% by weight.

[0298] Photo-crosslinkable adhesive A4 was obtained as a cured product of adhesive composition C4 in the form of an adhesive layer (substrate-less adhesive sheet) having a thickness of 150 μm sandwiched between release films R1 and R2 in the same manner as in Example 1 except that adhesive composition C4 was used instead of adhesive composition C1.

[0299] A laminate having a structure of PET film / adhesive layer / glass plate was prepared in the same manner as in Example 1 using the photo-crosslinkable adhesive A4.

[0300] <Measurement and evaluation>

[0301] (1) Determination of elastic modulus Gb' before photocrosslinking

[0302] The adhesives (adhesive sheets without substrates) involved in each example were stacked in a manner to a thickness of about 1.5 mm, and punched into a disc shape with a diameter of 7.9 mm to prepare a test sample. The test sample was clamped with parallel plates, and a shear strain with a frequency of 1 Hz was given using a viscoelasticity tester (ARES, manufactured by Rheometrics) while a dynamic viscoelasticity measurement was performed in a temperature range of -70 to 150°C and a heating rate of 5°C / min using a shear mode to obtain the shear storage elastic modulus Gb' at 80°C. The results are shown in Table 1.

[0303] (2) Determination of elastic modulus Gc' after photocrosslinking

[0304] The pressure-sensitive adhesive (pressure-sensitive adhesive sheet without substrate) according to each example was sandwiched between release films R1 and R2 and illuminated with the high-pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The test sample was prepared by irradiating ultraviolet rays from one side under the conditions of , and after photocrosslinking, the release films R1 and R2 were removed, overlapped in a manner of about 1.5 mm, and punched into a disk shape with a diameter of 7.9 mm. The dynamic viscoelasticity of the test sample was measured in the same manner as the measurement of the elastic modulus Gb' before photocrosslinking, and the shear storage elastic modulus Gc' at 80°C was obtained. The results are shown in Table 1.

[0305] (3) Determination of VOC emissions

[0306] The VOC emission of the PSA (PSA sheet without substrate) according to each example was measured according to the above-mentioned VOC measurement test.

[0307] (4) Durability evaluation

[0308] An aluminum foil (manufactured by Mitsubishi Aluminum Foil, trade name "NippakuFoil", thickness 12 μm) was bonded to one surface of a polarizing plate (manufactured by Nitto Denko, trade name "REGQ-HC3", thickness 92 mm) using a 15 μm thick adhesive, and the resulting product was used as an adherend to be bonded to one surface of a substrate-free pressure-sensitive adhesive sheet.

[0309] The adhesive (adhesive sheet without substrate) involved in each example was cut into a size of 60 mm × 120 mm together with the release films R1 and R2, and then the release film R2 was peeled off, and the exposed adhesive surface was bonded to the surface of the polarizing plate side of the above-mentioned adherend using a hand roller. Next, the release liner R2 was peeled off from the above-mentioned adhesive, and the exposed adhesive surface was bonded to a glass plate (manufactured by Matsunami Glass Industries, trade name "MICRO SLIDE GLASS", product number "S", thickness of 1.3 mm, haze of 0.1%, water-polished edge). As described above, a laminate having a structure of glass plate / adhesive / polarizing plate / aluminum foil was obtained.

[0310] The laminate was subjected to autoclave treatment (50°C, 0.5 MPa, 15 minutes) and then illuminated with the high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The glass plate was irradiated with ultraviolet rays from the side thereof under the conditions of , and the obtained product was used as a sample for durability evaluation.

[0311] After the evaluation sample was stored at 85°C for 24 hours, it was visually observed at 23°C and 50% RH, and the durability was evaluated at the following two levels. The results are shown in the "Adhesion Durability" column of Table 1. It should be noted that, when using any of the adhesive sheets involved in the examples, no bubbles were observed immediately after the above-mentioned durability evaluation samples were prepared.

[0312] E (Excellent): No bubbles were observed (excellent adhesion durability).

[0313] P (Poor): Generation of bubbles was clearly observed (insufficient adhesion durability).

[0314] (5) Peel strength

[0315] The release film R2 was peeled off from the adhesive (substrate-free adhesive sheet) of each example and attached to a corona-treated PET film having a thickness of 75 μm to prepare a single-sided adhesive sheet, which was cut into a size of 20 mm in width and 100 mm in length to prepare a test piece.

[0316] In an environment of 23°C and 50% RH, the peeling film R1 was peeled off from the test piece, and the exposed adhesive surface was pressed against a glass plate (Gorilla Glass 3 manufactured by Corning) as an adherend by reciprocating a 2 kg rubber roller. After autoclaving (50°C, 0.5 MPa, 15 minutes), the high pressure mercury lamp was used to heat the test piece at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The ultraviolet rays are irradiated from the glass plate side under the conditions.

[0317] Then, under the environment of 23°C and 50% RH, the peel strength of the test piece from the glass plate was measured using a tensile tester (manufactured by Minebea, universal tensile compression tester, device name "tensile compression tester, TCM-1kNB") at a tensile speed of 300 mm / min and a peeling angle of 180 degrees. The measurement was performed three times, and the average value thereof was converted into a value per width of 10 mm (unit: N / 10 mm) and is shown in Table 1.

[0318]

Table 1

[0319] Table 1

[0320]

[0321] As shown in Table 1, the photo-crosslinkable adhesives of Examples 1, 2, and 4 showed significantly superior adhesion durability compared to the adhesive of Example 3. In addition, the photo-crosslinkable adhesives of Examples 1, 2, and 4 emitted less VOC than the adhesive of Example 3 and had significantly lower odor.

[0322] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes examples obtained by variously modifying and changing the specific examples described above.

[0323] Description of Reference Numerals

[0324] 1, 2 adhesive sheets

[0325] 10 Adhesive layer

[0326] 10A One surface (bonding surface)

[0327] 10B Another Surface

[0328] 20 Substrate

[0329] 20A Side 1

[0330] 20B Second side (back side)

[0331] 30, 31, 32 Release liner

[0332] 50 Adhesive sheet with release liner

[0333] 70 Optical components

[0334] 100 Components with adhesive sheet

Claims

1. Photo-crosslinkable adhesive, The photo-crosslinkable adhesive is a cured product of an adhesive composition comprising an ethylenically unsaturated compound and a component containing a benzophenone structure, and comprises a polymer having a benzophenone structure in a side chain, and The emission of volatile organic compounds is less than 500 μg / g.

2. The photo-crosslinkable adhesive according to claim 1, wherein The benzophenone structure-containing component is a polymer having a benzophenone structure in a side chain.

3. The photo-crosslinkable adhesive according to claim 1 or 2, wherein The shear storage elastic modulus Gb' [kPa] of the photo-crosslinkable adhesive at 80°C and the 2 、Accumulated light intensity 10000mJ / cm 2 The relationship between the shear storage elastic modulus Gc' [kPa] at 80° C. of the photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays satisfies the following formula: Gc'[kPa]-Gb'[kPa]≥2kPa.

4. The photo-crosslinkable adhesive according to claim 1 or 2, wherein Use a high pressure mercury lamp with an illumination of 300mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The photo-crosslinked product obtained by irradiating the photo-crosslinkable adhesive with ultraviolet rays has a shear storage modulus Gc' [kPa] at 80° C. of 40 kPa or more. 5 . A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the photo-crosslinkable pressure-sensitive adhesive according to claim 1 .

6. The adhesive sheet according to claim 5, wherein The peel strength measured by the following procedure is 1.0 N / 10 mm or more. [Peel strength measurement procedure] The surface of the adhesive layer was pressed against the glass plate by reciprocating a 2 kg rubber roller once, and then autoclaved and heated with a high pressure mercury lamp at an illumination of 300 mW / cm 2 、Accumulated light intensity 10000mJ / cm 2 The glass plate was irradiated with ultraviolet rays from the side under the conditions of, and then, in an atmosphere of 25°C, the adhesive sheet was peeled off from the glass plate at a tensile speed of 300 mm / min and a peeling angle of 180 degrees, and the peel strength at this time was measured. The autoclave treatment was carried out under the conditions of 50°C, 0.5 MPa and 15 minutes.

7. A method for manufacturing a laminate, comprising: laminating the photo-crosslinkable adhesive according to any one of claims 1 to 4 and a member; as well as The benzophenone structure contained in the photo-crosslinkable adhesive is reacted to photo-crosslink the photo-crosslinkable adhesive.

8. A method for producing a photocrosslinkable adhesive, comprising: preparing an adhesive composition comprising a polymer (A) having a benzophenone structure in a side chain and an ethylenically unsaturated compound (B); as well as irradiating the adhesive composition with active energy rays, Here, the irradiation with the active energy rays is performed so that the ethylenically unsaturated group of the ethylenically unsaturated compound (B) reacts and the benzophenone structure of the polymer (A) remains.

9. The method of claim 8, wherein: The adhesive composition includes a compound (B1) having one ethylenically unsaturated group as the ethylenically unsaturated compound (B).

10. The method according to claim 8 or 9, wherein: The adhesive composition includes a compound (B2) having two or more ethylenically unsaturated groups as the ethylenically unsaturated compound (B).

11. The method according to claim 8 or 9, wherein: The adhesive composition further comprises a photoinitiator (C).

Citation Information

Patent Citations

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Active energy ray-curable composition and pressure-sensitive adhesive

    JP2012140497A

  • Beam member composite and floor structure

    JP2019143392A

  • Acrylic hot melt adhesives

    CN101595191A

  • Radiation curable pressure sensitive adhesive sheet

    JP2013040256A